Short fiber, fiber dispersion, and non-woven fabric
By using a fiber dispersion composed of high-flatness short fibers and specific polymers, the problem of poor fiber dispersion under high-speed stirring is solved, the homogeneity of the fiber dispersion and the complex void structure of the non-woven fabric are achieved, and the material's durability is improved. performance.
Patent Information
- Application Number
- CN202380045393.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-14
- Filing Date
- 2023-05-30
- Publication Date
- 2025-01-24
AI Technical Summary
The prior art is difficult to maintain the homogeneity of the fiber dispersion under high-speed stirring conditions, resulting in fiber entanglement and poor dispersion, which limits the widespread application of the fiber dispersion.
Using short fibers with high flatness, the ratio of the long axis length of the fiber cross section divided by the short axis length is more than 5, and the average short axis length is less than 2000nm, and through specific cross-sectional morphology and polymer composition, it is ensured Excellent dispersion of fibers in aqueous media.
Under extensive stirring conditions, short fibers can maintain a homogeneous dispersion state, avoid fiber entanglement, improve the performance of fiber dispersions, and obtain dense but complex non-woven fabrics with complex void structures through sheeting, significantly improving sound absorption and filtration. and separation performance.
Smart Images

Figure CN119365639A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to short fibers, fiber dispersions and nonwoven fabrics, and more particularly to short fibers suitable for fiber dispersions, fiber dispersions in which the short fibers are dispersed in an aqueous medium, and nonwoven fabrics composed of the short fibers and having a special structure with complex voids. Background Art
[0002] Since fibers have various characteristics derived from their elongated shape, they are not only used for clothing but are also widely used as industrial materials. As people live a more affluent life today, they are pursuing fiber products with multiple functions.
[0003] One of the characteristics of fiber morphology is that it has a large surface area per unit weight, that is, a large specific surface area. By utilizing this specific surface area, a high adsorption effect on the target substance and a high reinforcement effect when added as a filler can be obtained. Therefore, a variety of high-performance materials utilizing the specific surface area of fibers have been continuously studied.
[0004] As one of the developments of fiber products that utilize the specific surface area of fibers, there is a fiber dispersion in which short fibers cut into a desired length are dispersed in a medium. This dispersion itself can not only be used for the introduction of fillers into adsorbent materials or resin products, but can also be developed into high-performance filter materials or separation membranes by copying the dispersion and forming it into sheets using a wet papermaking method (also called wet papermaking method). Therefore, research and technical development on fiber dispersions are actively carried out.
[0005] As an indicator that determines the performance of the fiber dispersion, sometimes the fibers are evenly dispersed in the dispersion and their specific surface area can be fully utilized. However, due to the specific surface area of the mixed fibers, in addition to the fibers being easily agglomerated, the originally long and thin fibers are entangled with each other, and thus the dispersion state is easily made inhomogeneous. In order to maintain high-quality products or their formability, various technologies aimed at homogenizing the fiber dispersion have been proposed.
[0006] Patent Document 1 proposes a technique for producing ultrafine fibers that are advantageous in increasing the specific surface area. In ultrafine fibers, the cohesive force from intermolecular forces increases dramatically due to the increase in specific surface area, making it difficult to obtain a homogeneous dispersion. However, by shortening the fiber length to less than 1 mm, the fiber length becomes extremely short, and the fibers can be uniformly dispersed in the dispersion without causing bulk-like poor dispersion due to fiber entanglement.
[0007] Patent Document 2 relates to a technique for improving fiber dispersibility by actively causing electric repulsion to act between ultrafine fibers. By making the electric repulsion acting between the fibers larger than the cohesive force, uniform dispersion can be achieved even when the fibers are long.
[0008] Patent document 3 is a technology for processing short fibers in uneven thickness in the length direction to solve the problem of homogeneous dispersion in the dispersion liquid based on their morphological characteristics. By making a part of the length direction thicker and less prone to bending, the occurrence of block-like poor dispersion due to fiber entanglement can be suppressed.
[0009] Prior art literature
[0010] Patent Literature
[0011] Patent Document 1: Japanese Patent Application Publication No. 2007-107160
[0012] Patent Document 2: International Publication No. 2020-101002
[0013] Patent Document 3: Japanese Patent Application Publication No. 2018-84008
[0014] Invention Name
[0015] Problems to be solved by the invention
[0016] Patent Document 1 utilizes the following principle: as the fiber diameter decreases, the fiber becomes softer and more easily bendable, and the fibers are intricately entangled in the dispersion, which easily leads to bulk-like dispersion failure. Therefore, by shortening the fiber length, the fibers are less likely to be entangled.
[0017] That is, by reducing the aspect ratio, which is the value obtained by dividing the fiber length by the fiber diameter, the fibers are less likely to be entangled in the dispersion. However, in this method, although a uniform dispersion state can be obtained when stirring at a low speed, poor dispersion in which the fibers are entangled is likely to occur when stirring at a high speed, and dispersibility may become a problem. In particular, this poor dispersion tends to be prominent in ultrafine fibers, and the process that can be used to form a dispersion of ultrafine fibers may be limited.
[0018] In Patent Document 2, the electric repulsion between fibers is utilized to uniformly disperse the fibers by applying repulsive force between the fibers, making them difficult to settle and maintaining a dispersed state for a long time. However, when a force greater than the electric repulsion is applied by high-speed stirring, the fibers sometimes come into contact with each other and become fiber clumps, and sometimes the applicable process for forming a dispersion liquid is limited.
[0019] Patent Document 3 uses a roller press to break ultrafine fibers to produce ultrafine flat short fibers with uneven thickness in the length direction. The short fibers are partially thickened and difficult to bend, and the fibers are difficult to entangle. However, in the process of breaking the short fibers by a roller press, the upper limit of the thickness difference in the length direction of one short fiber is about 2 times. After all, during high-speed stirring, the fibers sometimes entangle with each other to form fiber blocks, and dispersibility becomes a problem.
[0020] As described above, as short fibers that are intended to be used in fiber dispersions, there are technologies for uniformly dispersing short fibers with a high specific surface area when left to stand or stirred at a low speed, but there is no technology for uniformly dispersing short fibers even when stirred at a high speed, and the production process of the fiber dispersion is limited. Therefore, according to recent demands, there is a need for short fibers that can be applied to a wide range of processes, can be developed in various application fields, and are suitable for fiber dispersions with excellent dispersibility.
[0021] Solution
[0022] In order to solve the above problems, the present invention has the following solutions.
[0023] [1] A short fiber having a flatness (i.e., a value obtained by dividing the length of the major axis of the fiber cross section by the length of the minor axis) of 5 or more, and an average value of the minor axis length of 2000 nm or less.
[0024] [2] The short fibers according to [1], wherein the CV value of the length variation of the minor axis of the fiber cross section is 10% or more.
[0025] [3] The short fibers according to [1] or [2], wherein the roughness of the fiber cross section is 20% or more.
[0026] [4] The short fibers as described in [1] have a crystallinity of 20% or less.
[0027] [5] The short fibers described in [4] have a melting point of 180°C or higher.
[0028] [6] A fiber dispersion liquid, which is obtained by dispersing the short fibers described in [1] or [4] in an aqueous medium.
[0029] [7] A nonwoven fabric comprising the short fibers described in [1] or [4] in at least a portion thereof.
[0030] [8]. A nonwoven fabric having a density of 0.4 g / cm 3 The average pore size is 6 μm or less, and the maximum frequency of the pore size distribution is 30% or less.
[0031] [9] The nonwoven fabric as described in [8], wherein the arithmetic mean roughness Ra of the surface is 5.00 μm or less.
[0032]
[10] . A fiber product comprising the nonwoven fabric described in [7] or [8] in at least a part thereof.
[0033] Effects of the Invention
[0034] The present invention relates to short fibers that exhibit excellent dispersibility in a liquid medium such as water due to the morphological characteristics of high flatness of the fiber cross section, and can provide a homogeneous fiber dispersion without entanglement of the short fibers even under a wide range of stirring conditions. In addition, by utilizing the excellent water dispersibility of the short fibers to form short fibers into sheets, a nonwoven fabric having a special structure with dense but complex voids can be obtained, which exhibits excellent characteristics in terms of sound absorption in low-frequency bands related to daily life noise, road noise, etc., and filtering and separation of specific components, and is expected to be widely developed and applied as an industrial material. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 This is a schematic diagram of an example of the cross-sectional structure of the short fiber of the present invention.
[0036] Figure 2 This is a schematic diagram for explaining the cross-sectional structure of the concavity and convexity of the short fiber of the present invention.
[0037] Figure 3 This is a schematic diagram of an example of the cross-sectional structure of a multi-layer laminated fiber used as a raw material of the staple fiber of the present invention.
[0038] Figure 4 This is a cross-sectional view for explaining an example of a method for producing a multi-layer laminated fiber.
[0039] Figure 5 The diagrams are characteristic diagrams showing the brightness histogram in a fiber dispersion liquid composed of short fibers of the present invention, wherein (a) is a schematic diagram of the brightness histogram of a fiber dispersion liquid in which the fibers are uniformly dispersed, and (b) is a schematic diagram of the brightness histogram of a fiber dispersion liquid when a fiber agglomerate is formed. DETAILED DESCRIPTION
[0040] Hereinafter, the present invention will be described in detail in conjunction with preferred embodiments.
[0041] The present invention relates to a short fiber characterized by excellent dispersibility in a liquid medium such as water. The short fiber referred to in the present invention refers to a fiber having a length of less than 100 mm and cut into a desired length along the length direction of the fiber.
[0042] The short fibers of the present invention utilize their high specific surface area to achieve high adsorption effect on target substances and high reinforcement effect when added as fillers. When the short fibers of the present invention are used as filter materials or separation membranes, the specific surface area of the short fibers is preferably 0.0010 nm from the viewpoint of improving their performance. -1 above.
[0043] In addition, the specific surface area mentioned here is calculated|required as follows.
[0044] The fiber bundle composed of the short fibers of the present invention is embedded with an embedding agent such as epoxy resin, the fiber cross section is cut out with a microtome equipped with a diamond knife and shaved, and the cross section is photographed with a scanning electron microscope (SEM) or the like at a magnification that allows the cross section to be identified.
[0045] For the cross section of a fiber present in the captured image, use image analysis software (WINROOF) to determine an arbitrary position on the periphery of the cross section as the measurement starting point, and trace the periphery with a series of images from the measurement starting point to measure the length until it returns to the measurement starting point. This value is set as the periphery length of one fiber, and is expressed as an integer in nm (rounded off below the decimal point). Use image analysis software (WINROOF) to measure the area of the inner part surrounded by the periphery, and this value is set as the cross-sectional area of one fiber, expressed in nm. 2 The unit is expressed as an integer (rounded off to the nearest decimal place). The specific surface area of one fiber is calculated by the following formula by rounding off to the nearest fifth decimal place using the outer circumference and cross-sectional area.
[0046] Specific surface area (nm -1 ) = outer perimeter (nm) / cross-sectional area (nm 2 )
[0047] The above measurement was performed on 100 fibers, the specific surface area of each fiber was calculated, and the arithmetic average thereof was taken as the specific surface area.
[0048] If the specific surface area is 0.0010nm -1 As described above, it is possible to achieve a specific surface area effect equivalent to that of ultrafine fibers having a fiber diameter of several μm, and to exhibit excellent adsorption performance and the like.
[0049] In addition, from this point of view, the effect of the present invention becomes more significant as the specific surface area increases. If the specific surface area is 0.0040 nm -1 Above, the excellent effect of nanofibers with a fiber diameter of several hundred nanometers is exerted, so it can be listed as a more preferred range. Furthermore, the specific surface area is 0.0080 nm -1 The above is a particularly preferred range of the present invention. If it is within this range, excellent effects can be exerted by mixing the short fibers of the present invention into fiber products. By utilizing this increased specific surface area, for example, even when formed as a material mixed with other aggregates, the filtration, separation, and adsorption performances are excellent, and specific performances are exerted. For example, even without surface treatment, ions in liquids can be captured, so it can be used for the recovery of valuables in seawater, etc., and can also be used for the adsorption of odor components in the air.
[0050] The short fibers of the present invention are characterized by their morphological characteristics, which, in addition to the improved performance of the above-mentioned fiber products, also have excellent dispersibility in liquid media such as water. As an important requirement for taking into account both the specific surface area and excellent dispersibility of the short fibers, which cannot be achieved in the prior art, the flatness, which is the value obtained by dividing the length of the major axis of the fiber cross section by the length of the minor axis, must be greater than 5. This is used as the first requirement of the present invention.
[0051] The flatness of the fiber cross section is determined as follows (see also Figure 1 ).
[0052] For the cross section of a fiber present in the image taken when calculating the specific surface area, the maximum length of the cross section is measured using image analysis software (WINROOF), and this value is used as the length of the major axis of a fiber, expressed as an integer in nm, and the decimal point is rounded off. Next, the length of the intersection of the line segment orthogonal to the line segment of the maximum length and the fiber cross section at the midpoint of the maximum length is measured, and this value is used as the length of the minor axis of a fiber, expressed as an integer in nm, and the decimal point is rounded off. Using the length of the major axis and the length of the minor axis, the flatness of a fiber is calculated by the following formula.
[0053] Flatness = major axis length (nm) / minor axis length (nm)
[0054] The above measurement was performed on 100 fibers, the flatness of each fiber was calculated, and the arithmetic mean value thereof was defined as the flatness.
[0055] The short fibers of the present invention need to have a flatness of 5 or more. Within this range, due to the morphological characteristics of the cross section, that is, the anisotropy of the cross section, the bending rigidity in the short axis direction and the long axis direction are significantly different, and when the fiber dispersion is prepared, the bending direction of the short fibers is limited to the short axis direction. Due to the limitation of the deformation direction, even if the short fibers are in contact with each other in the dispersion, poor dispersion due to the short fibers bending to form complex entangled blocks will not occur, and excellent dispersibility is exhibited.
[0056] Such short fibers of the present invention limit the bending direction by utilizing the shape anisotropy of the cross section, and the short fibers are difficult to entangle with each other in the dispersion. According to this technical idea, the higher the flatness of the cross section, the greater the difference in bending rigidity in the short axis direction and the long axis direction. When the fiber dispersion is made, the bending direction is firmly limited to the short axis direction. That is, if the flatness is 15 or more, the bending rigidity in the short axis direction and the long axis direction of the cross section differs by more than 200 times, and the bending direction of the short fibers in the dispersion is essentially limited only to the short axis direction. By firmly limiting the bending direction in the short axis direction in this way, even under high-speed stirring, it is difficult for the short fibers to entangle with each other in the dispersion, showing excellent dispersibility, so the flatness is preferably 15 or more.
[0057] Furthermore, if the flatness is 30 or more, even under high-speed stirring conditions such as defibration of short fiber bundles aggregated by cohesive forces such as intermolecular forces, the defibrated short fibers are less likely to be entangled with each other due to the restriction of the bending direction caused by the shape anisotropy of the cross section. From the viewpoint of obtaining excellent dispersibility under a wide range of stirring conditions including defibration, the flatness is more preferably 30 or more.
[0058] In addition, if the flatness is 50 or more, due to the shape anisotropy at this time, when the fiber dispersion is stirred, it is easy to obtain a flow state in which the short axis direction of the short fiber cross section is consistent due to the flow rate difference in the dispersion. In such a flow state, since the short axis directions are consistent, it is difficult for the short fibers to contact each other, and it is easy to obtain a homogeneous dispersion state, so the flatness is particularly preferably 50 or more.
[0059] On the other hand, as the flatness of the cross section increases, there is a tendency for cracks to form in the long axis direction of the cross section when external force is applied during the stirring process, etc. However, if the flatness is less than 800, there is no problem in actual use and the purpose of the present invention can be achieved.
[0060] As described above, due to the high shape anisotropy of the cross-section of the short fibers of the present invention, the bending direction in the dispersion is changed from all 360° directions to only the short axis direction compared to the conventional circular cross-section fibers, making it difficult to form block-like poor dispersion in which the short fibers are complexly entangled with each other. Even short fibers with a high specific surface area can exhibit excellent dispersibility under a wide range of stirring conditions.
[0061] The dispersibility of the short fibers is affected not only by the flatness of the cross section but also by the fiber diameter. In order to fully improve the dispersibility from the cross-sectional shape under a wide range of stirring conditions from low speed to high speed, the fiber diameter also becomes an important factor. As an indicator of the fiber diameter, in the short fibers of the present invention, the short axis length of the cross section is short as the second requirement, and the average value of the short axis length must be below 2000nm.
[0062] The average value of the minor axis length mentioned here is obtained by calculating the arithmetic mean value of the minor axis lengths of the 100 fibers measured above in units of nm and rounding off the decimal point to an integer.
[0063] In the short fibers of the present invention, when the average length of the minor axis is 2000 nm or less, the sedimentation rate of the fibers in the dispersion liquid becomes sufficiently slow, and the dispersion state of the fibers is maintained homogeneous.
[0064] According to this technical idea, the shorter the length of the short axis, the slower the sedimentation rate of the fiber, and the more difficult it is for the fiber to settle over time. Therefore, for the short fibers of the present invention, the average length of the short axis is preferably less than 1000nm. Within this range, the fibers will not settle even when stirred with weak force and can maintain a homogeneous dispersion state.
[0065] Furthermore, even when there is no stirring force for a short time during the fiber dispersion feeding step, the fibers will not settle as long as the average minor axis length is 500 nm or less, so this can be cited as a more preferred range in the present invention.
[0066] Furthermore, it is particularly preferred that the average length of the minor axis is 250 nm or less. Within this range, even when the fiber dispersion is stored without agitation for a long period of time, the fibers are unlikely to settle and a uniform dispersion state is maintained.
[0067] On the other hand, as a range in which the fibers are not easily broken when external force is applied in the stirring step or the like, the average length of the minor axis in the short fibers of the present invention is 20 nm or more, which is the substantial lower limit of the present invention.
[0068] The short fibers of the present invention have an ultra-flat cross section in which the long axis is extremely large relative to the short axis, so that the bending direction of the short fibers themselves is restricted. When dispersed in a liquid medium such as water, the range of conditions under which a homogeneous dispersion state can be maintained is much wider than that of the prior art, such as from high shear to low shear and increased stirring conditions. In this characteristic fiber cross section, from the viewpoint of suppressing the entanglement and adhesion of adjacent fibers and ensuring the dispersibility over time, it is preferred that the shape of the fiber cross section has a distribution state within a certain range, and in the short fibers of the present invention, the length of the short axis may vary.
[0069] The variability of the minor axis length (CV value) in the present invention refers to the calculation of the arithmetic mean and standard deviation of the minor axis lengths of the 100 fibers measured above, dividing the standard deviation by the arithmetic mean to obtain the coefficient of variation, and rounding off the decimal point to obtain an integer (in %).
[0070] By having the length of the short axis being appropriately distributed, in addition to being difficult to join due to the inconsistency of the cross-sectional shapes of the fibers, each short fiber moves differently when an external force such as shear is applied. For example, the buckling behavior of the short fibers when they are in contact with each other in a liquid medium differs, and the short fibers do not become entangled with each other, and a homogeneous state can be maintained over time. From the above viewpoints, in the short fibers of the present invention, the deviation of the length of the short axis is preferably 10% or more. By setting it within this range, even in a dispersion liquid to which short fibers that are easy to contact each other are added at a high concentration, since the bending behavior etc. are different in each fiber, entanglement etc. does not occur, and a homogeneous dispersion state can be ensured.
[0071] In addition, when the deviation of the short axis length is greater than 20%, the short fibers are unlikely to become entangled even in a clay-state fiber dispersion containing an extremely high concentration of short fibers relative to the medium, and excellent dispersibility can be achieved again by diluting the dispersion with a liquid, etc., so this can be listed as a more preferred range in the present invention.
[0072] Furthermore, in the present invention, it is particularly preferred that the deviation of the short axis length is greater than 30%. As long as it is within this range, even when the short fibers are dispersed into the medium from a coagulated short fiber bundle or fiber aggregate, the coagulation state can be eliminated by causing each short fiber to exhibit different behaviors and disperse by external force, and the short fibers can be easily dispersed by stirring for a short time.
[0073] To promote this view, the greater the deviation in the length of the short axis, the higher the dispersibility in the liquid medium. However, when external force is applied during a stirring process, the dispersion may become uneven, or the short axis may be too short, resulting in short fibers breaking. Therefore, the deviation in the length of the short axis is preferably less than 50%, which is the actual upper limit of the present invention.
[0074] In the short fibers of the present invention, in addition to suppressing the entanglement caused by the difference in the fiber cross-section of each short fiber, the presence of projections and depressions on the periphery of the flat cross-section can suppress the bonding and entanglement between the short fibers through stereoscopic barriers. Preferably, the projections and depressions on the fiber cross-section are greater than 20%.
[0075] The roughness in the present invention refers to the length of the intersection of the line segment orthogonal to the line segment of the maximum length and the fiber cross section at the points dividing the maximum length of the cross section into 10 equal parts, and the arithmetic mean and standard deviation of the lengths at these 10 points are calculated. The roughness of the single fiber is obtained in percentage by dividing the standard deviation by the arithmetic mean, and the value obtained by rounding off the decimal point is calculated (see also Figure 2 ). The same measurement is performed on 10 fiber cross sections, and the arithmetic average of the calculated concavity and convexity of the 10 fibers is used as the concavity and convexity mentioned here. When the concavity and convexity is 20% or more, the short fibers are easily dispersed starting from the tiny gaps between the fibers and can be evenly dispersed in a short time.
[0076] A high degree of roughness can suppress entanglement of short fibers, but the degree of roughness is within a range where cracking due to load concentration on a part of the cross section does not occur, and this can be the substantial upper limit of the present invention.
[0077] The short fibers of the present invention are derived from the fiber cross section, have a high specific surface area effect and excellent dispersibility that enables them to function effectively, are advantageous when added as fillers in resins, and can be used as high-functional nonwoven fabrics with separation, filtration, adsorption and other properties by sheeting.
[0078] In the case of a nonwoven fabric, the mechanical properties of the sheet are exerted by a bridge structure such as friction between adjacent short fibers, but the bridge structure refers to a structure in which short fibers present in a medium interact with each other to transmit force. Therefore, when short fibers of the same concentration exist in a medium, the thinner the fiber diameter and the longer the fiber length, the more a bridge structure is formed, which promotes the transmission of force. That is, the higher the ratio of fiber length to fiber diameter, the more the formation of the bridge structure is promoted. As an index, it can be said that in the short fibers of the present invention, the value obtained by dividing the fiber length by the length of the minor axis, that is, the aspect ratio is preferably high.
[0079] The aspect ratio in the present invention is calculated as follows.
[0080] An image of a fiber bundle consisting of the short fibers of the present invention is taken by a microscope at a magnification that enables observation of more than 10 short fibers whose full length can be measured. The fiber lengths of 10 short fibers randomly selected from the photographed short fiber images are measured. The fiber length referred to here refers to the length of one fiber in the length direction taken from a two-dimensionally photographed image, which is measured in mm using image analysis software (WINROOF), and the second decimal place is rounded off. The above operation is performed on 10 images taken in the same manner, and the arithmetic average of the fiber lengths of 100 fibers is taken as the fiber length of the present invention. Using the value converted to nm units of the fiber length and the average value of the minor axis length obtained above, the aspect ratio is calculated by the following formula, and the decimal places are rounded off.
[0081] Aspect ratio = fiber length (nm) / average of minor axis length (nm)
[0082] When the short fibers of the present invention are sheeted, the aspect ratio is preferably greater than 3000. Within this range, a bridging structure is fully formed between the short fibers, and the resulting nonwoven fabric exhibits mechanical properties at a level that poses no problem in actual use even without reinforcement using an adhesive or the like.
[0083] In addition, in the present invention, the aspect ratio of the short fibers is preferably greater than 6000. Within this range, not only can the mechanical properties be fully exerted when the sheets are made, but the shedding of the short fibers during the sheet-making process is also minimized, and the process passability is also excellent.
[0084] On the other hand, the aspect ratio of the short fibers is preferably 50,000 or less, which is the substantial upper limit of the present invention, as a range that is not limited by stirring conditions, does not cause entanglement between the short fibers in the dispersion, and can ensure good handling properties.
[0085] The polymer constituting the staple fiber of the present invention is preferably a polymer having excellent heat resistance and chemical resistance from the viewpoint of the purpose and effect of the present invention and the practical use as a fiber product. That is, the polymer constituting the staple fiber is preferably composed of at least one polymer selected from polyester, polyamide, polyphenylene sulfide, and polyolefin. In addition to the above advantages, since these polymers are thermoplastic, the staple fiber of the present invention can be manufactured by a melt spinning method with high productivity, and it is also preferred from the viewpoint of adjusting mechanical properties, such as making it highly oriented and crystallized in the stretching process.
[0086] In particular, from the perspective of ensuring dispersibility, the short fibers of the present invention are more preferably composed of polymers with a high elastic modulus such as polyester or polyphenylene sulfide, so that the bending of the fibers when external force is applied can be suppressed, and in the short fiber dispersion process, the occurrence of poor dispersion due to entanglement of the fibers can be effectively suppressed.
[0087] In addition, by selecting a polymer having a functional group such as a carboxyl terminal group that exerts an electric repulsion, such as polyester, a repulsive force is generated between fibers without causing aggregation, and a uniform dispersion state is easily achieved.
[0088] The staple fibers of the present invention are preferably dispersed in a medium to prepare a fiber dispersion. In this case, from the viewpoint of using the electrical repulsion of a dispersant or the like to disperse the staple fibers, it is more preferred that the medium be an aqueous medium. By preparing such a fiber dispersion, a material having specific properties in terms of adsorption or enhancement is obtained.
[0089] As described above, the staple fibers of the present invention, due to the anisotropy of the cross-section shape, can maintain a homogeneous dispersion state under a wide range of stirring conditions from high shear to low shear when dispersed in a liquid medium such as water. If this excellent water dispersibility is utilized, even in the sheeting process of the wet papermaking method with various shearing magnitudes, the staple fibers are spread in a homogeneous dispersion state, and the staple fibers are uniformly distributed without uneven distribution, so that a nonwoven fabric with a special structure that is dense but has complex voids can be obtained. Furthermore, in the process of spreading the fibers as a nonwoven fabric, due to the high flatness of the cross-sectional shape of the staple fibers, the minor axis direction of the cross section naturally remains consistent and densely stacked in the thickness direction of the nonwoven fabric, and combined with the effect of the homogeneous dispersion state, a special structure that cannot be achieved by the prior art is formed. Therefore, it is preferred to make a nonwoven fabric containing the staple fibers of the present invention.
[0090] The nonwoven fabric of the present invention is characterized by having a special structure with complex voids formed inside the dense fabric. The density of the nonwoven fabric is 0.4 g / cm 3 The above is the first requirement.
[0091] The nonwoven fabric density referred to in the present invention is determined as follows.
[0092] That is, weigh the nonwoven fabric cut into 250mm×250mm square and convert it into unit area (1m 2 ) and the first decimal place of the obtained value was rounded off to obtain the unit area of the nonwoven fabric. The thickness was measured in mm using a dial thickness gauge SM-114 (manufactured by TECLOCK, measuring sub-shape 10 mmφ, scale 0.01 mm, measuring force 2.5 N or less). This operation was performed at any 5 locations for each sample, and the third decimal place of the average was rounded off to the second decimal place, and the obtained value was used as the thickness of the nonwoven fabric.
[0093] The nonwoven fabric density was calculated by the following formula using the basis weight and thickness of the nonwoven fabric obtained by the above method: The density was calculated for 10 samples, and the simple average value thereof was rounded off to the third decimal place, and the obtained value was taken as the nonwoven fabric density.
[0094] Nonwoven fabric density (g / cm 3 ) = weight per unit area / thickness
[0095] The nonwoven fabric density of the nonwoven fabric of the present invention must be 0.4 g / cm 3 By keeping the nonwoven fabric within this range, even if the thickness of the nonwoven fabric is thin enough, the nonwoven fabric has a dense structure with few voids, so when used as a sound absorbing material, it can be expected that the sound absorption rate in the low frequency band will be improved. If the thickness of the nonwoven fabric is further reduced and the nonwoven fabric is placed in a limited space facing the external materials in the vehicle interior, the nonwoven fabric density is preferably 0.6 g / cm 3 From this point of view, the higher the nonwoven fabric density, the better, and the nonwoven fabric density is more preferably 1.0 g / cm 3 If the above is within this range, it becomes a very thin sheet that does not affect the design and structure of the structure. On the other hand, if it is the non-woven fabric of the present invention, since there are gaps that penetrate the sheet that are suitable for the sound absorption mechanism, it will not reflect the sound to be absorbed, and the purpose of the present invention can be well achieved.
[0096] The above nonwoven fabric density is based on the premise that the fibers constituting the sheet are dispersed, and can be achieved by appropriately adjusting the sheet thickness and unit weight. At this time, by setting the unit weight of the sheet to a certain degree, a microscopic space of a target size can be formed, thereby achieving a nonwoven fabric that maintains practical sheet strength. From the above viewpoints, the unit weight of the nonwoven fabric of the present invention is preferably 3 to 500 g / m 2 Within this range, the objective effect of the present invention can be prevented from being impaired, and a sheet in which each fiber exists stably and homogeneously can be obtained.
[0097] The second requirement of the special structure of the nonwoven fabric of the present invention is that the average pore size is 6 μm or less and the maximum frequency of the pore size distribution is 30% or less.
[0098] The pore size mentioned here refers to the value calculated by the bubble point method. As the bubble point method, for example, the porous material automatic pore measurement system Perm-Porometer (manufactured by PMI) can be used. In the measurement of the Perm-Porometer, the nonwoven fabric is impregnated with a liquid with a known surface tension value, and the gas is supplied from the upper side of the sheet while increasing the pressure, and the pore size is measured based on the relationship between the pressure and the surface tension of the liquid on the surface of the nonwoven fabric.
[0099] Specifically, the pore size was calculated using Perm-Porometer (manufactured by PMI Inc.), an automatic pore measurement system for porous materials.
[0100] Three nonwoven fabrics were cut out as samples for measurement, and the pore diameter distribution was measured using Galwick (surface tension: 16 mN / m) as a measurement liquid with known surface tension. The average flow diameter obtained by automatic calculation was set as the average pore size, and the value obtained by rounding the second decimal place of the average value of each sample to the first decimal place was used.
[0101] In addition, the frequency of the pore size distribution is expressed as % by converting the value obtained by automatic calculation into a percentage, and the value with the largest frequency of the pore size distribution is taken as the maximum frequency. Then, the average value of the maximum frequency of each sample is obtained, and the value obtained by rounding the second decimal place to the first decimal place is used.
[0102] The average pore size of the nonwoven fabric of the present invention must be 6 μm or less, and the maximum frequency of the pore size distribution must be 30% or less. Within this range, the void size contained in the nonwoven fabric is small, and there are various void sizes. Therefore, when used as a sound absorbing material, it can absorb sound widely in the low frequency band through a complex void structure.
[0103] Furthermore, in order to have a high sound absorption rate in a low frequency and wide frequency band, it is more preferable that the average pore size is 2 μm or less and the maximum frequency of the pore size distribution is 20% or less. As the lower limit for substantially fully achieving the purpose of the present invention, the average pore size is 0.1 μm or more and the maximum frequency of the pore size distribution is 10% or more. Within this range, effective sound absorption performance can be exerted without hindering the fluid.
[0104] The nonwoven fabric of the present invention exhibits excellent properties even when used alone as a sound absorbing material, but if it is envisioned that it is used in a recently developed sound absorbing material that is particularly suitable for electric vehicles, it can be conceived that it is used as a laminated material with other materials. In this case, when manufacturing a molded body, since it is bonded to other raw materials with an adhesive, from the viewpoint of improving the bonding strength with other raw materials, the arithmetic mean roughness (Ra) of the nonwoven fabric surface of the nonwoven fabric of the present invention is preferably 5.0 μm or less.
[0105] The arithmetic mean roughness (Ra) mentioned here is obtained as follows. That is, the surface of the nonwoven fabric is observed using a laser microscope (VK-X200 manufactured by Keyence or a laser microscope having equivalent performance), and the measurement is performed according to JIS B0601 using analysis software (VK-H1XA manufactured by Keyence or an analysis software having equivalent performance). The measurement is performed at any 5 locations for each sample, and the third decimal place of their average value is rounded off to the second decimal place, and the value obtained is taken as Ra.
[0106] In the present invention, setting the arithmetic mean roughness (Ra) of the nonwoven surface to 5.0 μm or less means that practical properties can be exhibited and the surface has sufficient smoothness. Since there are no rough bumps on the surface, it can be well integrated by laminating with other materials, and the resistance to peeling over time is also excellent. Furthermore, within this range, an appropriate effect is also exerted from the perspective of sound absorption. For example, when the nonwoven fabric of the present invention is used as a sound absorbing material, the diffuse reflection of sound waves on the surface can be suppressed, and sound can be effectively absorbed. From this point of view, in order to further suppress the diffuse reflection of sound waves on the surface, it is more preferred that the arithmetic mean roughness (Ra) of the nonwoven surface is 2.0 μm or less.
[0107] As described above, as a feature of the nonwoven fabric of the present invention, by utilizing a special structure that is dense but has complex voids formed inside, it is possible to exhibit excellent sound absorbing performance as a sound absorbing material, mainly in the low frequency band, and by designing the sheet structure and combining with other materials, it is possible to achieve a wide range of sound absorbing performance. In addition, in the special sheet structure formed on the nonwoven fabric of the present invention, it is excellent not only in general filtration but also in adsorption and filtration of valuables or harmful substances, and can be effectively used as a base material for a filter material.
[0108] Among various methods for producing nonwoven fabrics, in order to form the dense structure that is a characteristic of the nonwoven fabric of the present invention, it is preferred to use a wet method that is good at producing nonwoven fabrics with high density, that is, a wet papermaking method, thereby being able to stably produce the special sheet structure that is a characteristic of the present invention.
[0109] The characteristic of the nonwoven fabric of the present invention is to form a special structure of dense but fine gaps, which can be appropriately adjusted by adjusting the mixing ratio of various fibers constituting the nonwoven fabric or changing the cross-sectional morphology of the staple fibers of the present invention. In addition, from the perspective of the cross-sectional morphology of the staple fibers, the higher the flatness of the fiber cross section, the more uniformly the direction of the fiber cross section is spread, the more significant the effect is, the smaller the length of the minor axis of the fiber cross section, the better the fusion with other mixed materials by soft bending in the direction of the minor axis, and thus a more dense and complex nonwoven fabric with a gap structure can be obtained. In addition, since the deviation and concavity of the length of the minor axis of the fiber cross section are relatively large to a certain extent, it also plays a role of three-dimensional obstruction in the nonwoven fabric, and produces fine gaps between the staple fibers, which can make the special structure as the characteristic of the nonwoven fabric of the present invention significant.
[0110] As described above, the nonwoven fabric of the present invention, due to the high flatness of the short fibers in the cross-sectional shape, the short fibers with a high specific surface area are uniformly present without uneven distribution, and the direction of the flat cross-section is consistent and densely spread, resulting in a dramatic increase in the contact area between the fibers in the nonwoven fabric. By utilizing this feature to bond the fibers constituting the nonwoven fabric, a thin nonwoven fabric with excellent mechanical properties can be obtained.
[0111] That is, by using the short fibers of the present invention constituting the nonwoven fabric as adhesive fibers for bonding the fibers within the nonwoven fabric, excellent bonding properties can be exhibited even in a thin nonwoven fabric having a low weight per unit area, thereby obtaining a thin nonwoven fabric having excellent mechanical properties.
[0112] In the short fibers of the present invention, the crystallinity is preferably 20% or less from the viewpoint of exerting excellent thermal adhesiveness. In addition, the thermal adhesiveness mentioned here refers to the function of being able to bond and combine the bonded materials after being softened and flowed by heating and attached to the bonded materials, and then cooled and solidified.
[0113] When the staple fibers of the present invention are made into nonwoven fabrics, in addition to the large contact area between the fibers, the fibers can also exert thermal adhesiveness due to the morphological characteristics of the fibers, so that the fibers can be firmly bonded to each other, thereby increasing the strength of the nonwoven fabric. The thermal adhesiveness is also affected by the state of the staple fibers at each bonding point, and in order to fully exert the thermal adhesiveness, the fluidity of the fibers is also an important factor. As an indicator of the fluidity, the short fibers of the present invention preferably have a crystallinity of 20% or less.
[0114] The crystallinity here is determined as follows.
[0115] After weighing about 5 mg of short fibers using an electronic balance, the fibers were placed in a differential scanning calorimeter (DSC) and differential scanning calorimetry was performed under nitrogen at a heating rate of 16°C / min and a measurement temperature range of 50 to 320°C.
[0116] The crystallization heat ΔHc (J / g) is calculated from the area of the exothermic peak in the obtained measurement result (DSC curve), and the crystal melting heat ΔHm (J / g) is calculated from the area of the endothermic peak. In addition, when multiple exothermic peaks or endothermic peaks are observed, ΔHc and ΔHm are calculated based on the total value of the area of all peaks. The measurement position is changed 3 times for each level, and the arithmetic average is calculated. After calculating ΔHc and ΔHm, the crystallinity is calculated by rounding off the first decimal place using the following formula.
[0117] Crystallinity (%) = (ΔHm-ΔHc) / ΔHm 0 ×100
[0118] The ΔHm mentioned here 0 is the heat of complete crystallization and melting (J / g).
[0119] In the short fibers of the present invention, if the degree of crystallinity is less than 20%, when heated to above the glass transition temperature of the short fibers, the amorphous regions are not easily hindered by the crystalline regions and can fully soften and flow. Therefore, when hot pressing is performed through calendering or the like, the softened and flowed short fibers enter between the bonded materials and can exert high thermal bonding properties.
[0120] According to this technical concept, the thermoplastic fiber with a smaller degree of crystallinity softens and flows well during the thermal bonding process. In the short fibers of the present invention, the degree of crystallinity is more preferably below 15%. Within this range, it is easy to penetrate seamlessly even in the complex concave-convex of the bonded material, and can exhibit excellent thermal bonding properties regardless of the shape of the bonded material.
[0121] In addition, the degree of crystallinity is more preferably below 10%. If it is within this range, even when the hot pressing pressure of the calendering process is low, the softened and flowing short fibers can easily enter between the bonded materials, thereby reducing the adhesion to the rollers by hot pressing, thereby reducing the process tension and suppressing the breakage of thin sheets with low unit area weight during the manufacturing process.
[0122] Furthermore, it is particularly preferred that the crystallinity is 8% or less. Within this range, even with non-contact heating such as an oven without calendering, the thermoplastic fibers soften and flow to enter between the bonded materials, thereby exhibiting excellent thermal bonding properties.
[0123] As described above, the short fibers of the present invention, in addition to the effect of increasing the bonding area due to the morphological characteristics of the fibers, have good fluidity when heated due to the fiber structure, so that the thermoplastic fibers can seamlessly enter between the bonded materials and exert excellent thermal bonding properties. As a result, it is possible to achieve excellent mechanical properties of thin sheets with low weight per unit area that are difficult to achieve with the prior art.
[0124] Based on the viewpoint of achieving excellent thermal bonding through good fluidity during heating, in addition to the macroscopic irregularities between the bonded materials, it is preferred that the fine irregularities at the bonding points be seamlessly entered at the molecular level. As an indicator of this, the peak value of tanδ of the short fibers of the present invention is preferably above 0.10.
[0125] The tan δ mentioned here is measured using a dynamic viscoelasticity automatic measuring device (Leobion) by clamping a sample with a chuck distance of 30 mm, applying a tension of 0.07 g / dtex, and measuring at a heating rate of 3° C. / min and a frequency of 110 Hz.
[0126] The peak value of tanδ is equivalent to the amount of molecular chains that can move without restriction at this temperature. The larger the value, the easier it is for the material to flow at this temperature. If the peak value of tanδ is above 0.10, the softened and flowing short fibers can easily enter between the bonded materials and can firmly bond the bonded materials to each other. Therefore, it can be listed as a preferred range.
[0127] In addition, if the peak value of tan δ is 0.15 or more, the softened and fluidized short fibers can easily enter the unevenness of the surface of the adhered material, and the peeling of the short fibers bonded to the adhered material can be suppressed, so it can be listed as a more preferred range. If the peak value of tan δ is 0.20 or more, the fine unevenness of the surface of the adhered material can be entered at the molecular level, and the peeling of the adhered material and the bonded short fibers can be significantly suppressed, so it can be listed as a more preferred range.
[0128] The polymer constituting the staple fibers of the present invention is preferably a polymer having excellent heat resistance in view of practical use as a sheet or fiber product, and the melting point of the polymer constituting the staple fibers of the present invention is preferably 180° C. or higher.
[0129] The melting point of the polymer mentioned here is determined as follows.
[0130] The polymer was passed through a vacuum dryer to a moisture content of less than 200 ppm, and about 5 mg was weighed. Using a differential scanning calorimeter (DSC), the temperature was raised from 0°C to 320°C at a heating rate of 16°C / min, and then maintained at 320°C for 5 minutes for DSC measurement. The melting point was calculated based on the melting peak observed during the heating process. Each sample was measured 3 times, and the arithmetic mean was taken as the melting point of the polymer of the present invention. In addition, when multiple melting peaks were observed, the top of the melting peak on the highest temperature side was taken as the melting point.
[0131] Since the melting point of the polymer constituting the short fibers of the present invention is above 180°C, even when the sheet-like material composed of the short fibers is subjected to various processing and used, the short fibers are not easily softened by the heat in the processing steps, the adhesive force is not easily damaged, and excellent process passability can be exerted, so they can be listed as a preferred range.
[0132] In addition, since the melting point of the polymer constituting the short fibers is above 200°C, even when a film is formed by coating with other thermoplastic resins having a low melting point, the mechanical properties of the sheet are not easily impaired due to softening of the bonding points, and the sheet can pass the process well, so it can be listed as a more preferred range.
[0133] By making the melting point of the polymer constituting the short fibers above 220°C, the bonding points can be maintained in a fully solidified state even when the tension in the processing step where heat is applied as described above is high, and a variety of processes can be applied without damaging the mechanical properties. Therefore, it can be listed as a more preferred range.
[0134] In addition, the short fibers of the present invention maintain an amorphous state before the thermal bonding process and are thermally crystallized after the thermal bonding process, thereby achieving sufficient heat resistance in actual use even if strong thermal bonding is achieved in low-temperature heat treatment. Polymers based on the above reasons include polyethylene terephthalate or its copolymer, polyethylene naphthalate, and polyphenylene sulfide. If these polymers are used, the unstretched yarn after spinning is easy to maintain an amorphous state at room temperature, and after the bonded materials are firmly bonded by softening and flowing due to glass transition, excellent heat resistance and chemical resistance can be exerted by crystallization.
[0135] As described above, by using the short fibers of the present invention as the binder fibers for bonding the fibers in the nonwoven fabric, a structure in which the fibers of the skeleton are firmly and evenly bonded is formed in the nonwoven fabric. As an indicator of this structure, the outer circumference length P of the fiber cross section in the cross section of the nonwoven fabric is m With P m The bonding length P in contact with the bonding part b The ratio of bonding rate P b / P m The degree of variation is preferably 80% or less.
[0136] The bonding portion referred to here refers to the portion where the binder fibers constituting the nonwoven fabric are softened and flowed by heating, thereby bonding the adjacent skeleton fibers to each other. In the bonding portion, the binder fibers may completely lose the fiber form before softening and flowing, or may maintain a part of the fiber form. b / P m The degree of variation of is calculated as follows.
[0137] The nonwoven fabric of the present invention is cut with a razor or the like to obtain a cross section, and the cross section is photographed with a scanning electron microscope (SEM) at a magnification that allows observation of the entire thickness direction of the nonwoven fabric.
[0138] For the cross section of one fiber (bone fiber) present in the captured image, the length of the outer periphery of the cross section was measured using image analysis software (WINROOF). This value was defined as the outer periphery length P of one fiber. m1 The perimeter P is expressed in μm and the third decimal place is rounded off. The perimeter P is measured using image analysis software (WINROOF). m1The length of the outer peripheral portion bonded to the binder fiber is defined as the bonding length P of one fiber. b1 , expressed in μm, and the third decimal place is rounded off. In addition, in the cross section of the nonwoven fabric, the binder fiber exists in the form of being impregnated between the skeleton fibers by softening and flowing in the thermal bonding process (although there are cases where the fiber form is no longer maintained, for convenience, it is sometimes recorded as binder fiber below), but between the skeleton fibers and the binder fibers impregnated therein, a contrast is obtained due to the difference in concavity and convexity, so the interface between the skeleton fibers and the binder fibers can be identified. Using this outer perimeter P mn and bonding length P bn The bonding rate P of one fiber is calculated as an integer (round off the decimal point) using the following formula: bn / P mn .
[0139] P bn / P mn (%) = P bn (μm) / P mn (μm)×100
[0140] The above measurement is performed on 100 fibers, and the bonding ratio Pbn / Pmn (n=1 to 100) of each bone fiber is calculated. The arithmetic mean and standard deviation thereof are calculated, and the coefficient of variation obtained by dividing the standard deviation by the arithmetic mean is defined as the bonding ratio P in the present invention. b / P m The degree of change is calculated by rounding off the decimal point to an integer (in %).
[0141] In order for the nonwoven fabric of the present invention to exhibit excellent mechanical properties, it is preferred that the skeleton fibers are uniformly bonded to each other throughout the nonwoven fabric. The bonding ratio P is used as an index for this. b / P m The degree of variation is preferably 80% or less. Within this range, the proportion of the skeleton fibers not bonded by the binder fibers is small, and the skeleton fibers are unlikely to fall off from each other, thereby achieving excellent mechanical properties.
[0142] According to this technical idea, the bonding rate P b / P m The smaller the variation of the bonding rate P, the more uniformly the skeleton fibers are bonded to each other in the nonwoven fabric as a whole, and excellent mechanical properties are exerted. The bonding rate P is more preferably b / P m The degree of variation is 70% or less. Within this range, a certain bonding length can be ensured by the skeleton fibers of the entire nonwoven fabric, and the nonwoven fabric is unlikely to be destroyed by bonding points with extremely short bonding lengths.
[0143] Adhesion rate P b / Pm The degree of variation is more preferably 60% or less. If it is within this range, the stress can be uniformly borne by the skeleton fibers of the entire nonwoven fabric, so even a thin nonwoven fabric with a low weight per unit area can exhibit excellent mechanical properties.
[0144] In addition, from the viewpoint of the bonding strength between the skeleton fiber and the binder fiber at each bonding point, the bonding ratio P b / P m The higher the better, the bonding rate P b / P m When the content is 25% or more, the aggregate fibers are firmly bonded by the binder fibers and are not easily peeled off at the interface. Therefore, this can be cited as a preferred range.
[0145] Furthermore, if the bonding rate P b / P m If it is 30% or more, the bonding points are firmly bonded to such an extent that the destruction of the sheet is caused by the destruction of the bone fiber itself, and the mechanical properties of the bone fiber can be fully utilized as the mechanical properties of the sheet. Therefore, it can be cited as a more preferred range.
[0146] An example of a method for producing the staple fibers and nonwoven fabric of the present invention will be described in detail below.
[0147] The method for producing short fibers of the present invention can be produced by cutting long fibers having the characteristic cross-sectional shape of the present invention into desired lengths. Specifically, the long fibers are bundled into a bundle of dozens to tens of thousands of fibers, and the bundles are cut into desired fiber lengths using a cutting machine such as a girotin cutter, a slicer, or a cryogenic cutter. Among the long fibers mentioned here, fibers composed of a single polymer may also be spun, but according to the prior art, fibers having a minor axis length of less than 2000 nm, which is a characteristic of the present invention, may be spun without any problems in terms of operability, which sometimes results in restrictions on spun conditions. Therefore, it is preferred to use, for example, a multilayer laminated fiber ( Figure 3 ) by removing a readily soluble polymer from the mixture to produce fibers having a flat fiber cross section.
[0148] The multi-layer stacked fibers mentioned in the present invention refer to fibers having a fiber cross-section with a multi-layer stacked structure in which two or more polymers are alternately stacked in the same order or in different orders. The form of the stacked structure may be not only fibers in which poorly soluble polymers and easily soluble polymers are alternately stacked in one direction, but also fibers stacked radially from the center of the fiber to the outside, fibers stacked irregularly on the fiber cross-section, or fibers formed by a combination of these.
[0149] The method for producing the multi-layer laminated fiber of the present invention can be appropriately selected according to the overall production apparatus and the polymer used, but a melt spinning method is preferably used from the viewpoint of excellent productivity.
[0150] The multi-layer laminated fiber obtained by the melt spinning method can be made into silk with melt-molded polymers such as polyethylene terephthalate or its copolymer, polyethylene naphthalate, polybutylene terephthalate, polypropylene terephthalate, polypropylene, polyolefin, polycarbonate, polyacrylate, polyamide, polyphenylene sulfide, polylactic acid, thermoplastic polyurethane, etc. In addition, these polymers can contain various additives such as inorganic substances such as titanium oxide, silicon dioxide, barium oxide, colorants such as carbon black, dyes or pigments, flame retardants, fluorescent whitening agents, antioxidants or ultraviolet absorbers. In addition, in the case of selecting a polymer containing these additives, concavities and convexities are generated in each layer of the multi-layer laminated fiber corresponding to the particle size of the microparticles as the additive, and arbitrary concavities and convexities can be given to the generated fiber on this basis.
[0151] The multilayer laminated fiber is manufactured by selecting two or more polymers from the above polymers for spinning, but the combination of polymers is also important from the viewpoint of forming a stable laminated structure. That is, the smaller the difference in solubility parameter (SP value) of the combined polymers, the better the laminated structure can be formed, such as no confluence between layers, and the polymers are preferably selected in such a way that the difference in solubility parameter between the two polymers forming the interface is 3.0 or less.
[0152] The solubility parameter (SP value) mentioned here refers to a parameter reflecting the cohesive force of a substance defined by (evaporation energy / molar volume) 1 / 2, and can be calculated, for example, based on the values recorded in "Plastic Databook" (Plastic Data Book) co-edited by Asahi Kasei Amidis Corporation / Plastics Editorial Department, page 189, etc. The absolute value of the value obtained by subtracting the solubility parameter of one component from the solubility parameter of another component is the solubility parameter difference mentioned in the present invention.
[0153] In addition, by using polymers with different solubility, the easily soluble polymers of the multi-layer laminated fibers can be removed, and short fibers composed of poorly soluble polymers can be effectively produced. For example, if the polymers constituting the multi-layer laminated fibers are set to alkali-soluble polyesters and alkali-poorly soluble polyesters, or alkali-soluble polyesters and polyphenylene sulfide (alkali-poorly soluble), or alkali-soluble polyesters and polyamides (alkali-poorly soluble), short fibers composed of poorly soluble polymers can be well produced by alkali reduction treatment. In particular, as a readily soluble polyester, from the viewpoint of spinnability and simple dissolution in a low-concentration aqueous solvent, it is preferred to use a polyester formed by copolymerizing polyethylene glycol or sodium sulfonate-based isophthalic acid alone or in combination. Examples of combinations of polymers suitable for producing short fibers from multi-layered laminated fibers include, in view of the relationship between melting points, polyethylene terephthalate copolymerized with 5 mol % to 15 mol % of 5-sodium sulfonate isophthalic acid as the easily soluble component, and polyethylene terephthalate copolymerized with 5 wt % to 15 wt % of polyethylene glycol having a weight average molecular weight of 500 to 3000 in addition to the above-mentioned 5-sodium sulfonate isophthalic acid, and polyethylene terephthalate, or polyphenylene sulfide, or polyamide-6 as the poorly soluble component.
[0154] The spinning temperature when spinning multi-layer laminated fibers, among more than two kinds of polymers, mainly takes the temperature at which a high melting point polymer or a high viscosity polymer shows fluidity. As the temperature showing the fluidity, it varies according to the molecular weight, but it is better to set it above the melting point of the polymer and below the melting point + 60 ° C. If it is below, the polymer will not be thermally decomposed in the spinneret or spinning assembly, and the molecular weight reduction can be suppressed, so it is preferred. As the ejection amount when spinning multi-layer laminated fibers, it can be stably manufactured by setting it to 0.1g / min·hole~20.0g / min·hole. In addition, the ratio of component A and component B can be selected in the range of 5 / 95~95 / 5 based on the ejection amount, with the weight ratio of component A / component B. When a poorly soluble polymer is used as component A and a readily soluble polymer is used as component B, and when short fibers are produced from multi-layer stacked fibers, a higher ratio of the poorly soluble polymer is preferred from the perspective of the productivity of the flat ultrafine fibers. If the component A / component B ratio is 50 / 50 to 90 / 10, multi-layer stacked fibers can be stably obtained without interrupting part of the stacked structure, and short fibers can be obtained with high production efficiency.
[0155] By inserting a polymer melted and having fluidity at the above spinning temperature into a spinneret to form a composite flow, a fiber with a multi-layered cross section can be manufactured. Here, as the spinneret used, a conventionally known composite die that composites two or more polymers can be used for spinning, but in order to stably form a special multi-layered cross section, the following composite die is preferably used.
[0156] The composite die preferably used in the present invention is preferably used as follows Figure 4 The composite die shown here is a laminated die consisting of three components: a metering plate D, a composite plate E, and a blowout plate F. Figure 4 This is an example using two types of polymers, namely, component A and component B. However, if necessary, three or more types of polymers may be used to produce the yarn.
[0157] In the composite die, the composite plate E is measured by the measuring plate D to evaluate the polymer amount of each hole, and the different types of polymer flows measured by the composite plate E are merged to form a composite flow, and the number of layers constituting the composite flow is multiplied by dividing and re-merging them, and the composite merged flow formed by the composite plate E is compressed and ejected by the ejection plate F. In addition, the composite flow mentioned here refers to a fluid composed of two or more polymers in a cross section perpendicular to the flow direction.
[0158] As the fine flow path of the composite plate E, a flow path structure that minimizes the flow turbulence in the flow path can be formed to produce multi-layer laminated fibers. In addition, the above-mentioned fine flow path can be said to have the same characteristics as the conventional static mixer (static mixer) in that the fluid is merged or divided in the flow path, but the general static mixer is a flow path designed for the purpose of mixing two polymers, and the interface of the laminated composite flow is prone to turbulence. In order to prevent this phenomenon, it is preferred to adopt a method using a composite die as described above.
[0159] In order to avoid making the description of the composite die complicated, although not shown in the figure, the components stacked on the metering plate D can be any components that form a corresponding flow path in coordination with the spinning machine and the spinning assembly. By designing the metering plate D to match the existing flow path components, the existing spinning assembly and its components can be directly used. Therefore, there is no need to make the spinning machine exclusive for this die.
[0160] In fact, multiple flow path plates can be stacked between the flow path and the metering plate D, or between the metering plate D and the composite plate E. The purpose is to provide a flow path that effectively transports the polymer in the cross-sectional direction of the die and the cross-sectional direction of the single fiber, and to introduce the polymer into the composite plate E.
[0161] The composite flow ejected from the ejection plate F is cooled and solidified, and is given an oil agent and pulled by a roller with a specified circumferential speed to form a composite fiber. The pulling speed can be determined by the ejection amount and the target fiber diameter, but in order to stably manufacture the composite fiber used in the present invention, it is preferably in the range of 100 to 7000 m / min. In addition, in the case of using it as an adhesive fiber that exerts thermal adhesiveness, it is more preferably pulled as an undrawn yarn in the range of 100 to 3000 m / min. In addition, from the viewpoint of making the multi-layer laminated fiber form a high orientation and improving the mechanical properties, it is better to stretch it. The stretching can be carried out after temporary winding in the spinning process, or it can be continued without temporary winding. As the stretching conditions, for example, in a stretching machine composed of a pair of rollers or more, if the fiber is a general thermoplastic polymer capable of melt spinning, the fiber can be stretched in the axial direction without any strain by setting the first roller at a temperature not less than the glass transition temperature and not more than the melting point and the second roller at a temperature corresponding to the crystallization temperature, and can be heat-set and wound to obtain a fiber having a Figure 3 The upper limit of the temperature of the first roller is preferably set to a temperature at which the fiber yarn path is not disturbed during the preheating process. For example, in the case of polyethylene terephthalate having a glass transition temperature of about 70°C, the preheating temperature is usually set to about 80 to 95°C. In addition, when it is assumed to be used as a binder fiber, the crystallinity of the fiber can be maintained low by using it as an undrawn yarn without drawing.
[0162] The above description is an example of using a melt spinning method, but as long as the above-mentioned composite die is used, even a spinning method using a solvent such as solution spinning can of course produce the multi-layer laminated fiber used in the present invention. The obtained multi-layer laminated fibers are bundled into a bundle of tens to tens of thousands of fibers, cut into a desired fiber length, and the easily soluble polymer is removed, thereby obtaining the short fiber of the present invention.
[0163] In order to obtain a fiber dispersion liquid composed of the staple fibers of the present invention, the multilayer laminated fibers cut into the desired fiber length can be immersed in a solvent that can dissolve the readily soluble polymer, and the readily soluble polymer can be removed. When the readily soluble polymer is a copolymerized polyethylene terephthalate formed by copolymerizing 5-sodium sulfonate isophthalic acid and / or polyethylene glycol, an alkaline aqueous solution such as an aqueous sodium hydroxide solution can be used. At this time, the bath ratio of the multilayer laminated fibers to the alkaline aqueous solution (weight of the multilayer laminated fibers (g) / weight of the alkaline aqueous solution (g)) is preferably 1 / 10000 to 1 / 5, and more preferably 1 / 5000 to 1 / 10. By staying within this range, poor dispersion of blocks caused by entanglement of the staple fibers when the readily soluble polymer is dissolved can be prevented.
[0164] The alkali concentration of the alkali aqueous solution at this time is preferably 0.1 to 10% by weight, and more preferably 0.5 to 5% by weight. By being within this range, the dissolution of the easily soluble polymer can be completed in a short time, and a fiber dispersion liquid in which the short fibers of the present invention are uniformly dispersed can be obtained without unnecessary degradation of the poorly soluble polymer. In addition, there is no particular limitation on the temperature of the alkali aqueous solution, and by setting it to above 50°C, the dissolution of the easily soluble polymer can be accelerated. In addition, in the case of using it as an adhesive fiber, at this time, if the alkali aqueous solution is set to 40 to 70°C, it is possible to accelerate the hydrolysis while maintaining the low crystallinity of the fiber, so it is preferred.
[0165] In such a fiber dispersion, in order to suppress the aggregation and sedimentation of the short fibers over time or the increase in the viscosity of the medium, additives may be used in the fiber dispersion as needed. As types of additives, natural polymers, synthetic polymers, organic compounds and inorganic compounds can be listed. For example, as additives for suppressing the aggregation of fibers, cationic compounds, nonionic compounds, anionic compounds, etc. can be listed. Such additives are preferably 0.001 to 10 equivalents relative to the weight of the short fibers. Within this range, the function can be fully imparted.
[0166] The medium may be neutralized with an acid such as hydrochloric acid or acetic acid, or may be diluted with water after the dehydration step. It is preferred to neutralize the medium in terms of operability.
[0167] As described above, not only can the fiber dispersion obtained by uniformly dispersing the short fibers of the present invention in a medium be directly utilized as a high-performance adsorbent material or reinforcing material, but also when the dispersion is used as a fiber aggregate after the medium is removed by a wet papermaking method or a spraying method, it can be widely expanded to high-performance filter materials, separation membranes, sound-absorbing materials, etc.
[0168] In the case of forming a nonwoven fabric by a wet papermaking method, for example, the skeleton fibers constituting the skeleton of the nonwoven fabric, the binder fibers for bonding the short fibers by heat treatment, and the functional short fibers for forming a special structure are put into water, and a pulping process or a refining process is performed as needed, and then stirred to make paper using a papermaking stock solution in which various short fibers are uniformly dispersed. In addition, in the process of preparing the papermaking stock solution, the dispersibility can be adjusted by the amount of short fibers added, the amount of water medium, the stirring time, etc., and it is preferably prepared according to the dispersion state of various short fibers.
[0169] Furthermore, a dispersant may be contained as necessary in order to suppress aggregation of short fibers put into water and stably produce a nonwoven fabric having a dense structure.
[0170] As the types of dispersants, natural polymers, synthetic polymers, organic compounds and inorganic compounds can be listed. For example, as additives for inhibiting the aggregation of fibers, cationic compounds, nonionic compounds, anionic compounds, etc. can be listed. Among them, in order to improve dispersibility, anionic compounds are preferably used from the viewpoint of electrical repulsion in an aqueous medium. In the manufacture of the present invention, the amount of dispersant added is preferably 0.001 to 10 equivalents relative to the weight of the fibers constituting the nonwoven fabric. Within this range, the processability of wet papermaking will not be impaired, the dispersibility of the fibers can be improved, and the nonwoven fabric of the present invention can be manufactured.
[0171] In the method for producing nonwoven fabrics, when wet papermaking is adopted, the various short fibers used in the papermaking stock solution preferably have a fiber length of 0.3 to 30.0 mm. Within this range, dispersibility in the papermaking stock solution can be maintained and wet papermaking can be performed well.
[0172] The fiber length of the short fibers can be appropriately adjusted according to their intended use. Generally, as the fiber length increases, the entanglement between the short fibers increases, and the mechanical properties and morphological stability of the nonwoven fabric tend to improve. However, since the short fibers tend to entangle and agglomerate during the stirring of the papermaking solution, it is better to make adjustments accordingly according to the style of the short fibers mixed in the papermaking solution and the expected design.
[0173] From the viewpoint of stabilizing the form of the nonwoven fabric in actual use and improving the mechanical properties, it is preferred to mix the binder fiber at 5 to 70% by weight. If it is within this range, the dense structure of the nonwoven fabric can be fixed, the sheet strength can be improved, and the smoothness of the surface of the nonwoven fabric can be improved. Furthermore, for the purpose of serving as the skeleton of the nonwoven fabric, skeleton fibers can be mixed as other fibers, and the weight can be appropriately adjusted to 10 to 95% relative to the total weight of the nonwoven fabric. As other fibers, when skeleton fibers are mixed, the short fibers of the present invention form a bridging structure with skeleton fibers at both ends, and the short fibers are filled between the skeleton fibers, thereby making it possible to manufacture a nonwoven fabric with complex fine gaps.
[0174] The fiber diameter and fiber cross-section of the skeleton fiber and the binder fiber mentioned here can be appropriately selected according to the purpose. However, in order to produce a nonwoven fabric having a special structure that is dense but has complex voids formed inside, which is a characteristic of the present invention, it is also preferred to use fibers with a flat cross-section in which the major axis length is longer than the minor axis length among the skeleton fiber and the binder fiber. In this case, a stacked structure can be smoothly formed with the short fibers of the present invention, and a nonwoven fabric with excellent density can be produced.
[0175] After the papermaking stock solution prepared with the above-mentioned various short fibers is diluted to a certain concentration, it is dehydrated on an inclined metal wire, a round screen, etc. to form a nonwoven fabric. As the device for papermaking, a round screen papermaking machine, a long-net papermaking machine, an inclined short-net papermaking machine, or a papermaking machine composed of these, etc. can be listed. In the papermaking process, in addition to considering the dispersibility of the fiber in the papermaking stock solution, the papermaking speed, the amount of fiber, and the amount of water medium should be adjusted according to the desired unit area weight to control the aggregation of the fibers during filtration. The sheet formed here is subjected to a drying process and a heat treatment process to remove moisture and bond the adhesive fibers to manufacture the nonwoven fabric of the present invention. As the drying method, from the viewpoint of being able to simultaneously implement the drying of the sheet and the thermal bonding of the adhesive fibers, it is preferred to adopt a method using hot air ventilation (circulating air) or a method of contacting it with a hot rotating roller (hot calendering roller, etc.).
[0176] Example
[0177] The short fibers of the present invention will be specifically described below with reference to Examples.
[0178] The following evaluations were performed on Examples and Comparative Examples.
[0179] A. Melt viscosity of polymer
[0180] The polymer crumbs were passed through a vacuum dryer to reduce the moisture content to 200 ppm or less, and the strain rate was measured using a Toyo Seiki melt viscosity meter, Capilog 1B, at a rate of 216 s. -1 In addition, the measurement temperature is made the same as the spinning temperature, and 1216s is recorded in the examples or comparative examples. -1 The melt viscosity of the sample was 5 minutes from the time the sample was placed in the heating furnace to the start of the measurement, and the measurement was performed in a nitrogen atmosphere.
[0181] B. Melting point of polymer
[0182] The chip-shaped polymer is passed through a vacuum dryer to make its moisture content less than 200ppm, weighing about 5mg, using a differential scanning calorimeter (DSC) Q2000 produced by TA INS TULMANT, after heating from 0°C to 300°C at a heating rate of 16°C / minute, it is kept at 300°C for 5 minutes and DSC is measured. The melting point is calculated according to the melting peak observed during the heating process. Each sample is measured 3 times, and its average value is used as the melting point. In addition, when multiple melting peaks are observed, the top of the melting peak on the highest temperature side is used as the melting point.
[0183] C. Poor solubility parameters
[0184] The solubility parameter (SP value) is a parameter reflecting the cohesive force of a substance defined by the square root of (evaporation energy / molar volume), and is obtained by immersing a polymer in various solvents and obtaining the value of (evaporation energy / molar volume) of the solvent when the swelling pressure becomes maximum as the (evaporation energy / molar volume) of the polymer. The SP value thus obtained is described in, for example, "Plastic Databook" (Plastic Databook), co-authored by Asahi Kasei Amidis Co., Ltd. / Plastics Editorial Department, page 189, and this value is used. In addition, the solubility parameter difference of the combined polymers is calculated as the absolute value of (SP value of component A - SP value of component B).
[0185] D. Fineness
[0186] The weight of 100 m of the composite fiber was measured and the value multiplied by 100 was calculated. The measurement was repeated 10 times and the average value was taken as the fineness (dtex). In addition, the value obtained by dividing the fineness by the number of filaments was taken as the single fiber fineness (dtex).
[0187] E. Specific surface area
[0188] The fiber bundle consisting of short fibers was embedded with an embedding agent such as epoxy resin, frozen with a cryostat FC·4E manufactured by Reichert, cut with a Reichert-Nissei ultracut N (ultra-thin slicer) equipped with a diamond knife, and then the cut surface was imaged with a H-7100FA transmission electron microscope (TEM) manufactured by Hitachi, Ltd. at a magnification that enables the cross section to be identified. Using image analysis software (WINROOF), an arbitrary position on the periphery of the cross section was determined as the measurement starting point, and the periphery was tracked with a series of images from the measurement starting point to measure the length until it returned to the measurement starting point again. This value was used as the periphery length of one fiber and was expressed as an integer in nm (rounded off below the decimal point). In addition, the area of the inner portion surrounded by the outer perimeter was measured using image analysis software (WINROOF), and this value was taken as the cross-sectional area of one fiber and expressed in nm. 2 The unit is expressed as an integer (rounded off to the nearest decimal place). The specific surface area of one fiber is calculated by the following formula using the outer circumference and the cross-sectional area, and the fifth decimal place is rounded off.
[0189] Specific surface area (nm -1 ) = outer perimeter (nm) / cross-sectional area (nm 2 )
[0190] The above measurement is performed on 100 fibers, the specific surface area of each fiber is calculated, and the arithmetic average thereof is taken as the specific surface area of the present invention.
[0191] F. Flatness
[0192] For the above-photographed fiber cross section, use image analysis software (WINROOF) to measure the maximum length of the cross section of the single fiber, and use this value as the length of the long axis of the single fiber to obtain an integer in nm (round off the decimal point). Next, measure the length of the intersection of the line segment orthogonal to the line segment of the maximum length and the fiber cross section at the midpoint of the maximum length, and use this value as the length of the short axis of the single fiber, and obtain an integer in nm (round off the decimal point). Using the length of the long axis and the length of the short axis, the flatness of the single fiber is calculated by the following formula.
[0193] Flatness = length in the major axis direction (nm) / length in the minor axis direction (nm)
[0194] The above measurement was performed on 100 fibers, the flatness of each fiber was calculated, and the arithmetic mean value was rounded off to the nearest decimal point to calculate the flatness.
[0195] G. Average of minor axis length
[0196] The arithmetic mean of the minor axis lengths of the 100 fibers measured above was calculated as an integer (rounded off to the nearest decimal point) in nm to calculate the average minor axis length.
[0197] H. Variation of minor axis length (CV value)
[0198] The arithmetic mean and standard deviation were calculated using the measured minor axis lengths of the 100 fibers, and the coefficient of variation obtained by dividing the standard deviation by the arithmetic mean was expressed as an integer (rounded off to the nearest decimal point) to calculate the degree of variation in the minor axis length.
[0199] I. Concavity
[0200] Using the image of the fiber cross section taken as described above, the lengths of the intersections of the line segments orthogonal to the line segments of the maximum length and the fiber cross section at the points that divide the maximum length of the cross section into 10 equal parts are measured, and the arithmetic mean and standard deviation of the lengths at these 10 points are calculated. The standard deviation is divided by the arithmetic mean, and the calculation is performed in percentage units and after the decimal point is rounded off, and the obtained value is used as the concavity and convexity of the single fiber (also refer to Figure 2 ). The same measurement is performed on 10 fiber cross sections, and the arithmetic mean of the roughness of the 10 single fibers is calculated as the roughness.
[0201] J. Aspect Ratio
[0202] The fiber bundle composed of short fibers is imaged through a microscope at a magnification that enables observation of more than 10 short fibers whose total length can be measured. The fiber lengths of 10 short fibers randomly selected from the captured short fiber images are measured. The fiber length referred to here refers to the length of one fiber in the length direction taken from the two-dimensional image, measured in mm using image analysis software, and rounded to the second decimal place. The above operation is also performed on the 10 images obtained by the capture, and the arithmetic mean of the fiber lengths of 100 fibers is taken as the fiber length of the present invention. The value converted to nm for the fiber length and the average value of the short axis length obtained above are used to calculate the aspect ratio by the following formula, and the decimal places are rounded to the nearest whole number.
[0203] Aspect ratio = fiber length (nm) / average value of minor axis length (nm)
[0204] K. Dispersion index under low speed stirring
[0205] The fiber dispersion was dispersed in an aqueous medium in such a manner that the short fiber concentration was 0.01% by weight relative to the total fiber dispersion, and then stirred at 100 rpm for 30 seconds using a stirrer and placed in a 20 mL spiral vial manufactured by Azuwo Co., Ltd. The spiral vial was photographed using a digital camera under illumination transmitted from the side of the spiral vial. The obtained image was converted into a monochrome image using image processing software (WINROOF), and a brightness histogram with a level of 256 was obtained (vertical axis: frequency (number of pixels), horizontal axis: brightness, also refer to Figure 5 ), calculate the standard deviation of the brightness value in one image. Perform the same operation on 10 images, take the arithmetic average of the standard deviation of the brightness value of each image, round off to the second decimal place, and use the obtained value as the dispersibility index under low-speed stirring.
[0206] L. Dispersion index under high-speed stirring
[0207] The fiber dispersion was dispersed in an aqueous medium in such a manner that the short fiber concentration was 0.01% by weight relative to the total fiber dispersion. After stirring at 19,000 rpm for 30 seconds using a stirrer, the fiber dispersion was placed in a 20 mL spiral vial manufactured by Azuwo Co., Ltd. The spiral vial was photographed using a digital camera under illumination transmitted from the side of the spiral vial. The obtained image was converted into a monochrome image using image processing software (WINROOF), and a brightness histogram with a level of 256 was obtained (vertical axis: frequency (number of pixels), horizontal axis: brightness, also refer to Figure 5 ), calculate the standard deviation of the brightness value in one image. Perform the same operation on 10 images, take the arithmetic average of the standard deviation of the brightness value of each image, round off to the second decimal place, and use the obtained value as the dispersibility index under high-speed stirring.
[0208] Dispersion evaluation
[0209] The dispersibility was evaluated according to the following criteria using the dispersion index under low-speed stirring and the dispersion index under high-speed stirring measured as described above.
[0210] Good: The dispersion index under low-speed stirring is less than 30, and the dispersion index under high-speed stirring is less than 30
[0211] Poor: Either the dispersion index under low-speed stirring or the dispersion index under high-speed stirring is 30 or more.
[0212] N. Average pore size and maximum frequency of pore size distribution
[0213] The pore size was calculated using the porous material automatic pore measurement system Perm-Porometer (manufactured by PMI) according to the bubble point method (based on ASTM F-316-86). Three nonwoven fabrics were cut out as the measurement samples, and the pore diameter distribution was measured using Galwick (surface tension: 16 mN / m) as the measurement liquid with known surface tension. The average flow diameter obtained by automatic calculation was used as the average pore size, and the value of the average value of each sample was rounded off to the first decimal place.
[0214] In addition, for the frequency of pore size distribution, the value obtained by automatic calculation is divided into a grade width of 0.1 μm and the value with the largest frequency of pore size distribution is taken as the maximum frequency. Then, it is converted into a percentage, and the average value of the maximum frequency of each sample is expressed as %, and the value obtained by rounding the second decimal place of the value to the first decimal place is used.
[0215] O.Weight per unit area
[0216] Weigh the nonwoven fabric cut into 250mm×250mm square and convert it into unit area (1m 2 ) is calculated, the value is rounded to the first decimal place, and the resulting integer is used as the weight per unit area of the nonwoven fabric.
[0217] P.Thickness
[0218] The thickness of the nonwoven fabric was measured in mm using a dial thickness gauge SM-114 (manufactured by TECLOCK, measuring sub-shape 10 mmφ, scale 0.01 mm, measuring force 2.5 N or less). This operation was performed at 5 random locations for each sample, and the average value was rounded off to the second decimal place, and the obtained value was taken as the thickness of the nonwoven fabric.
[0219] Q.Nonwoven fabric density
[0220] The density is calculated from the basis weight and thickness of the nonwoven fabric using the formula (1). The value is obtained for 10 samples, and the simple average is rounded off to the third decimal place to obtain the value as the density of the nonwoven fabric.
[0221] R. Arithmetic mean roughness of nonwoven surface (Ra)
[0222] The nonwoven surface was observed using a laser microscope VK-X200 (manufactured by Keyence Corporation), and the measurement was performed using analysis software VK-H1XA (manufactured by Keyence Corporation) in accordance with JIS B 0601. For each sample, the measurement was performed at 5 random locations, and the average value was rounded off to the second decimal place from the third decimal place, and the value obtained was defined as Ra.
[0223] S.Sound absorption rate
[0224] The measurement was performed according to JIS A 1405-1 (2007) "Method for determination of sound absorption of building materials by the in-pipe method" using an "automatic vertical incidence sound absorption meter" manufactured by Denshokuki Co., Ltd. For each nonwoven fabric sample, a solid cotton with a thickness of 20 mm composed of PET fibers with a fiber diameter of 15 μm was prepared as a support, and each nonwoven fabric sample was bonded to the support. The above measurement was performed on 10 samples and evaluated, and the sound absorption at 1000 Hz was expressed in %, and the sound absorption was calculated to the first decimal place. The first decimal place of the simple average value was rounded off, and the obtained value was used as the sound absorption.
[0225] T. Crystallinity
[0226] After using an electronic balance to weigh about 5 mg of thermoplastic fiber, the fiber was placed in a differential scanning calorimeter (DSC) Q2000 produced by TA Instruments, and differential scanning calorimetry was performed under nitrogen, at a heating rate of 16°C / min, and in a measuring temperature range of 50 to 320°C.
[0227] The crystallization heat ΔHc (J / g) is calculated from the area of the exothermic peak in the obtained measurement result (DSC curve), and the crystal melting heat ΔHm (J / g) is calculated from the area of the endothermic peak. In addition, when multiple exothermic peaks or endothermic peaks are observed, ΔHc and ΔHm are calculated based on the value of the total area of all peaks. After 3 measurements are performed for each horizontal change of the measurement position, the arithmetic mean is calculated to calculate ΔHc and ΔHm, and the crystallinity is calculated by rounding off the first decimal place using the following formula.
[0228] Crystallinity (%) = (ΔHm-ΔHc) / ΔHm 0 ×100
[0229] The ΔHm mentioned here 0 It is the heat of complete crystallization fusion (J / g). In the case of PET, 140.1 (J / g) is used, and in the case of PPS, 146.2 (J / g) is used.
[0230] U.tanδ
[0231] The dynamic viscoelasticity of the fiber was measured using Leo Biolon DOV-II-EP manufactured by Olientech Co., Ltd. After the sample was clamped with a chuck distance of 30 mm, a tension of 0.07 g / dtex was applied, and the measurement was performed under the conditions of a temperature increase rate of 3°C / min and a frequency of 110 Hz, and the peak temperature and peak value of tanδ at this time were evaluated.
[0232] V. Adhesion rate and adhesion rate variability
[0233] The nonwoven fabric was cut with a razor or the like to obtain a cross section, and the cross section was photographed with a scanning electron microscope S-5500 (SEM) manufactured by Hitachi HiTech Nologics Co., Ltd. at a magnification that enables observation of the entire thickness direction of the sheet. For the cross section of one bone material fiber present in the photographic image, the length of the outer periphery of the cross section was measured using image analysis software (WINROOF). This value was set as the outer periphery length P of one fiber. m1 The perimeter P is expressed in μm and the third decimal place is rounded off. The perimeter P is measured using image analysis software (WINROOF). m1 The length of the outer peripheral portion bonded to the binder fiber is taken as the bonding length P of one fiber. b1 , expressed in μm, and the third decimal place is rounded off. In addition, in the cross section of the nonwoven fabric, the binder fibers soften and flow through the thermal bonding process and exist in the form of being impregnated between the skeleton fibers, but the skeleton fibers and the binder fibers impregnated therein have a contrast due to the difference in concavity and convexity, so the interface between the skeleton fibers and the binder fibers can be identified. Using this outer perimeter P mn and bonding length P bn The bonding rate P of one fiber is calculated as an integer (round off the decimal point) using the following formula: bn / P mn .
[0234] P bn / P mn (%) = P bn (μm) / P mn (μm)×100
[0235] The above measurement was performed on 100 fibers, and the bonding rate P of each bone fiber was calculated. bn / P mn(n = 1 to 100), and their arithmetic mean is defined as the bonding rate P of the present invention. b / P m The standard deviation is calculated in the same way. The standard deviation is divided by the arithmetic mean, and the obtained coefficient of variation is expressed in % and rounded off to an integer. The obtained value is the adhesion ratio P in the present invention. b / P m The degree of change.
[0236] W. Uniformity
[0237] The uniformity of the sheet cut into a 250 mm×250 mm square was evaluated by visual observation on the following three scales.
[0238] A: There are no fiber lumps in the sheet and the uniformity is good.
[0239] B: Fiber masses can be seen within the flakes.
[0240] C: Fiber masses can be seen in the sheet, and cracks or pinholes are generated.
[0241] X. Strength
[0242] The maximum point load was measured using a universal testing machine Tensilon UTM-III-100 manufactured by Olientec Co., Ltd. under the conditions of a sample width of 15 mm, an initial length of 20 mm, and a tensile speed of 20 mm / min. The simple numerical average of the five measured values was obtained to calculate the strength of the sheet (N / 15 mm), which was expressed with the first decimal place rounded off.
[0243] [Example 1]
[0244] As component A, polyethylene terephthalate (PET, melt viscosity: 120 Pa·s, melting point: 254° C., SP value: 21.4 MPa) was prepared. 1 / 2 ), as component B, polyethylene terephthalate (SSIA-PEG copolymer PET, melt viscosity: 95 Pa·s, melting point: 233°C, SP value: 22.9 MPa) copolymerized with 8.0 mol% of 5-sodium sulfonate isophthalic acid and 9 wt% of polyethylene glycol was prepared. 1 / 2 ). In addition, the difference in solubility parameters of these polymers is 1.5 MPa 1 / 2 .
[0245] After the A component and the B component were melted at 290°C, the mixture was poured into a pre-assembled Figure 4The spinning assembly of the composite die shown in the figure ejects the composite polymer flow from the ejection hole. In addition, a fine flow path G capable of alternately stacking 128 layers of two components is used on the composite plate, such as Figure 3 As shown, two polymers are ejected in a composite form of alternately stacked multiple layers in one direction. After the ejected composite polymer flow is cooled and solidified, an oil agent is applied, and it is wound at a spinning speed of 1000m / min to collect undrawn yarns of 200dtex-24 filaments (total ejection amount 20g / min). The wound undrawn fibers are stretched 3.6 times between rollers heated to 90°C and 130°C to obtain stretched fibers of 56dtex-24 filaments.
[0246] The obtained multilayer laminated fibers were cut into a fiber length of 0.6 mm, and the cut multilayer laminated fibers were immersed in a 1 wt % sodium hydroxide aqueous solution (bath ratio 1 / 100) heated to 90° C. for 30 minutes to dissolve and remove more than 99% of the easily soluble polymer SSIA-PEG copolymer PET, thereby obtaining Figure 1 The cross section shown is of a flattened staple fiber.
[0247] The specific surface area was measured from the cross section of the obtained short fibers and was 0.0108 nm. -1 , which is very large. The cross-sectional morphology is a band-shaped cross-section with significantly different lengths of the major axis and the minor axis, with a flatness of 80 and an average length of the minor axis of 188nm. In addition, the variation of the length of the minor axis of the cross-section is 36%, and the concavity is 30%, which has a moderate variation in the length of the minor axis, and the surface has moderate concavities. In addition, the crystallinity is 36%, which is a state in which crystallization is fully carried out, and the melting point is 254°C.
[0248] A fiber dispersion liquid dispersed in an aqueous medium is prepared from the staple fibers, and the staple fiber concentration is 0.01% by weight relative to the total fiber dispersion liquid. The dispersion state after stirring at each speed is evaluated by image processing. At this time, if the fiber dispersion is homogeneous, there is no big difference in light and dark, so the standard deviation of brightness (dispersion index) becomes smaller. On the other hand, if the fiber dispersion is heterogeneous, there is a difference in light and dark locally, and the standard deviation of brightness (dispersion index) becomes larger. The dispersion index was evaluated, and the dispersion index at low speed was 7, and the dispersion index at high speed was 8. Regardless of the stirring speed, the fibers are uniformly dispersed, and both the specific surface area and excellent dispersibility of the staple fibers can be taken into account. The results are shown in Table 1.
[0249] [Examples 2, 3, 4]
[0250] In the method described in Example 1, all the steps were carried out in the same manner as in Example 1, except that the composite plate having the micro-channels in which the two components were alternately stacked was changed to 64 layers (Example 2), 32 layers (Example 3), and 16 layers (Example 4). These multi-layered fibers were subjected to the same cutting and dissolving treatment as above to obtain Figure 1 The cross-sectional shape shown is a flat short fiber. The evaluation results of these short fibers are shown in Table 1, but in all of Examples 2 to 4, they have a large specific surface area that is larger than that of general ultrafine fibers. In addition, the cross-sectional shape is an extremely thin band with high flatness, and has a moderate variation and unevenness of the short axis length. Compared with Example 1, although the dispersion index under low-speed and high-speed stirring becomes slightly larger as the flatness decreases and the average length of the short axis increases, it is able to have both the specific surface area and excellent dispersibility of the short fibers. In addition, the crystallinity of the short fibers is 36% and the melting point is 254°C.
[0251] [Example 5]
[0252] In the method described in Example 1, all are implemented in the same manner as in Example 1 except that it is changed to a composite plate having a micro-flow path in which two components are alternately stacked 512 layers (Example 5). The multi-layer stacked fibers are subjected to the same cutting and dissolution treatment as described above to obtain short fibers with a flat cross-sectional shape. The evaluation results of the short fibers are shown in Table 1, but they have a very large specific surface area far exceeding that of nanofibers with a fiber diameter of hundreds of nm, and the cross-sectional shape is an extremely thin ribbon with extremely high flatness. The dispersion index was evaluated, and the dispersion index at low speed was 5, and the dispersion index at high speed was 18. The dispersion index was increased by high-speed stirring, but there was no block-shaped poor dispersion that became a problem, and the large specific surface area and excellent dispersibility of the short fibers were taken into account. In addition, the crystallinity of the short fibers was 36% and the melting point was 254°C.
[0253] [Comparative Example 1]
[0254] In the method described in Example 1, a spinning assembly for 15 filaments with a 1000 island-type sea-island composite die in which component A is an island component and component B is a sea component was used, and the composite ratio of component A / B was set to 50 / 50, and the total ejection amount was 42 g / min. All other operations were carried out in the same manner as in Example 1. The sea-island composite fiber was subjected to the same cutting and dissolution treatment as described above to obtain a circular cross-section nanofiber (crystallinity: 36%, melting point: 254°C). The evaluation results of the nanofiber are shown in Table 1. Although the specific surface area is large, the high-speed stirring produces poor dispersion of blocks in which the fibers are entangled with each other, and the dispersibility is evaluated as significantly low.
[0255] [Comparative Example 2]
[0256] In the method described in Comparative Example 1, except that the cross-sectional shape of the island component was set to a flat cross-section, all other operations were carried out in the same manner as in Comparative Example 1. Although nanofibers with a large specific surface area and a flat cross-sectional shape (crystallinity: 36%, melting point: 254°C) were obtained, due to the low flatness, the fibers were entangled with each other by high-speed stirring in the same manner as in Comparative Example 1, and the dispersibility was significantly reduced.
[0257]
[0258] [Examples 6 and 7]
[0259] In the method described in Example 1, all the methods are implemented in the same manner as in Example 1 except that a composite plate having a different flow path structure from that of the micro-flow path G is used (Examples 6 and 7). The evaluation results of the obtained short fibers are shown in Table 2. The short fibers have the same extremely thin cross-sectional shape with high flatness as in Example 1, but the flow path structure of the composite plate is changed to be uniform with small variability and unevenness in the length of the short axis. When evaluating the dispersion index, since the variability and unevenness in the length of the short axis are smaller than those in Example 1, the value of the dispersion index is slightly larger than that in Example 1, but no obvious poor dispersion of the block is found, and the dispersibility is excellent. In addition, the crystallinity of the short fibers is 36% and the melting point is 254°C.
[0260] [Examples 8 and 9]
[0261] In the method described in Example 1, except for cutting and processing into fiber lengths of 1.8 mm (Example 8) and 5.0 mm (Example 9), all are implemented in the same way as in Example 1. In Example 8, even in the case of a large aspect ratio, the fibers are not entangled with each other due to the dispersion effect from the cross-sectional shape, and the dispersibility is excellent. In addition, in Example 9, because the aspect ratio is larger than that of Example 8, it can be seen that the dispersibility in high-speed stirring tends to deteriorate to some extent, but no block-shaped poor dispersion that becomes a problem is found, and the specific surface area of the short fiber and the excellent dispersibility can be taken into account. In addition, the crystallinity of the short fiber is 36% and the melting point is 254°C.
[0262] [Comparative Example 4]
[0263] In the method described in Comparative Example 1, all the steps were carried out in the same manner as in Comparative Example 1 except that the fiber length was cut to 5.0 mm. In Comparative Example 4, since the aspect ratio was larger than that in Comparative Example 1, even in low-speed stirring, the fibers were significantly entangled with each other, resulting in poor dispersion in the form of blocks, and the dispersibility was significantly poor. In addition, the crystallinity of the short fibers was 36%, and the melting point was 254°C.
[0264] Table 2
[0265]
[0266] Note 1) PET: Polyethylene terephthalate, Note 2) Fiber diameter
[0267] [Example 10]
[0268] The component A is composed of polyethylene terephthalate (PET, melting point: 254°C), and the component B is composed of polyethylene terephthalate copolymerized with 8.0 mol% of 5-sodium sulfonylisophthalic acid and 9 wt% of polyethylene glycol (SSIA-PEG copolymerized PET). Figure 3 The multilayer laminated fiber formed by alternately laminating two polymers in one direction as shown was cut to a fiber length of 0.6 mm, and the multilayer laminated fiber was dissolved by a 1 wt % sodium hydroxide aqueous solution (bath ratio 1 / 100) heated to 90°C to obtain a dispersion containing flat fibers (minor axis length: 1000 nm) with a flatness of 20 as functional fibers. In addition, the obtained flat fiber had a crystallinity of 36%, indicating that crystallization was fully progressed, and a melting point of 254°C.
[0269] Next, a dispersion of cut fibers (core component having a fiber diameter of 10 μm and a fiber length of 5.0 mm) containing heat-fusible core-sheath composite fibers (core component: PET, sheath component: polyester (copolyester) having a melting point of 110°C copolymerized in a ratio of 60 mol % of terephthalic acid, 40 mol % of isophthalic acid, 85 mol % of ethylene glycol and 15 mol % of diethylene glycol) as a binder fiber is prepared, and then the flat fiber dispersion and the cut fiber dispersion are uniformly mixed and dispersed with water through a dissociation step and a pulping step in such a way that the mixing ratio of the cut fibers is 30 weight % and the mixing ratio of the flat fibers is 70%, thereby producing a papermaking stock solution.
[0270] A square sheet machine (250 mm square) manufactured by Kumagai Riki Industry Co., Ltd. was used to prepare the sheet with a unit weight of 50 g / m 2 The papermaking stock solution was used for papermaking in a manner of , and dried and heat-treated in a rotary dryer with a roll temperature set at 110° C., thereby obtaining a nonwoven fabric.
[0271] The obtained nonwoven fabric has a uniformly oriented flat fiber structure with a dense cross-sectional direction, a thickness of 105 μm, and a nonwoven fabric density of 0.48 g / cm 3 . The average pore size calculated by the bubble point method is 0.5μm, and the maximum frequency of the pore size distribution is 17.9%, which is a nonwoven fabric with dense spaces having various micropores. In addition, Ra is 2.96μm, and it has a smooth surface. The sound absorption rate at 1000Hz is 82%, and it is a nonwoven fabric with excellent sound absorption properties in the low frequency band. The results are shown in Table 3.
[0272] [Examples 11 and 12]
[0273] In addition to changing the unit area weight of the non-woven fabric to 25g / m 2 (Example 11), 5g / m 2 Except for (Example 12), the same implementation is carried out as in Example 10.
[0274] The obtained nonwoven fabric has the same orientation of flat fibers (crystallinity: 36%, melting point: 254°C) as in Example 10, and has a dense structure in the cross-sectional direction. The evaluation results of these nonwoven fabrics are shown in Table 3, but when the weight per unit area is reduced, the density of the nonwoven fabric is reduced and the average pore size is increased, so the density is reduced compared with Example 10. However, the sound absorption rate at 1000 Hz is 66% or more, and it is a nonwoven fabric with excellent sound absorption that is effective in practical use.
[0275] [Examples 13 to 15]
[0276] As shown in Table 3, the same procedures as in Example 10 were followed except that the flatness and the minor axis length of the functional fibers (flat fibers) constituting the nonwoven fabric were variously changed (Examples 13 to 15).
[0277] The obtained nonwoven fabric has the same orientation of flat fibers (crystallinity: 36%, melting point: 254°C) as in Examples 10 to 12, and has a dense structure in the cross-sectional direction. The evaluation results of these nonwoven fabrics are shown in Table 3, but compared with Example 10, when the flatness is increased, the density of the nonwoven fabric increases, and the average pore size increases, so the density is improved compared with Example 10. In addition, the maximum frequency of the pore size distribution is reduced, and it is a nonwoven fabric with a more complex void structure. Moreover, since the short axis of the flat fiber is shortened, Ra is reduced, and it is a nonwoven fabric with a smaller surface roughness than Example 10.
[0278] [Example 16]
[0279] The process was carried out according to Example 10 except that the flatness of the flat fibers constituting the nonwoven fabric was changed to 10. The obtained nonwoven fabric was the same as that of Examples 10 to 15, and the orientation of the flat fibers was consistent, and it had a dense structure in the cross-sectional direction. The evaluation results of the nonwoven fabric are shown in Table 3, but compared with Example 10, when the flatness was reduced, the density of the nonwoven fabric increased, and the average pore size increased, so the density was slightly reduced compared with Example 10, but there was no problem in practical use, and the requirements of the nonwoven fabric of the present invention were met. The results are shown in Table 3. In addition, the crystallinity of the flat fibers was 36% and the melting point was 254°C.
[0280] [Example 17]
[0281] The process is carried out in accordance with Example 10, except that the flat fibers (crystallinity: 36%, melting point: 254°C) used in Example 10 are used as functional fibers constituting the nonwoven fabric, and further, the binder fibers used in Example 10 and ultrafine PET fibers with a fiber diameter of 0.3 μm are used as other fibers, and papermaking is carried out by preparing a papermaking solution in a mixing ratio of functional fibers (flat fibers) / binder fibers / other fibers (ultrafine fibers) = 60 wt % / 30 wt % / 10 wt %.
[0282] The obtained nonwoven fabric is the same as Examples 10 to 16, with the short axis of the flat fibers overlapped perpendicularly to the thickness direction, and has a dense structure in which ultrafine fibers exist in a bridged state with the skeleton fibers as the foothold. The evaluation results of the nonwoven fabric are shown in Table 3, but since the ultrafine fibers exist in a bridged state, it is a nonwoven fabric with a denser structure than Example 10. On the other hand, the void structure is made uniform by the ultrafine fibers, and the maximum frequency of the pore size distribution is higher than that of Example 10. In particular, in Example 17, in addition to the densification of the nonwoven fabric structure using flat fibers mixed as functional fibers, it also has a structure in which ultrafine fibers mixed as other fibers are arranged in the voids, showing extremely excellent sound absorption. Furthermore, the pore size is also small, and it has a special void structure, and it can also be expected to exhibit excellent characteristics in terms of filtration, separation and other performances.
[0283]
[0284] [Comparative Example 4]
[0285] The procedure of Example 10 was followed except that the fibers (bone fibers) constituting the nonwoven fabric were changed to ultrafine fibers (PET, crystallinity: 36%, melting point: 254° C.) having a fiber diameter of 3.0 μm.
[0286] The thickness of the obtained nonwoven fabric was 220 μm and the density of the nonwoven fabric was 0.23 g / cm 3 The average pore size calculated by the bubble point method was 14.3 μm, which was a nonwoven fabric with low density and coarse voids compared with Example 10. In addition, Ra was 13.62 μm, indicating a rough surface. The results are shown in Table 4.
[0287] [Comparative Example 5]
[0288] As the fibers constituting the nonwoven fabric, the skeleton fiber used was an ultrafine fiber with a fiber diameter of 3.0 μm, and the functional fiber used was the flat fiber used in Example 10 (crystallinity: 36%, melting point: 254°C). Papermaking was carried out in a ratio of skeleton fiber / binder fiber / flat fiber = 60 wt % / 30 wt % / 10 wt %, and the rest was carried out in accordance with Example 10.
[0289] The obtained nonwoven fabric has a low mixing ratio of flat fibers, so the thickness is 197 μm and the density is 0.25 g / cm 3 The average pore size calculated by the bubble point method was 12.3 μm, and the nonwoven fabric had low density and coarse voids, similar to Comparative Example 4. The results are shown in Table 4.
[0290] [Comparative Example 6]
[0291] The same procedure as in Example 10 was carried out except that the flatness of the flat fibers constituting the nonwoven fabric was set to 2. The flat fibers had a crystallinity of 36% and a melting point of 254°C.
[0292] The obtained nonwoven fabric has a thickness of 264 μm and a density of 0.19 g / cm2 due to the small flatness of the flat fibers. 3 The average pore size calculated by the bubble point method was 29.6 μm, and the nonwoven fabric had a low density and contained larger pores than those in Comparative Examples 4 and 5. The results are shown in Table 4.
[0293] Table 4
[0294]
[0295] Note 1) PET: Polyethylene terephthalate, Note 2) Fiber diameter: 3.0 μm
[0296] [Example 18]
[0297] As the skeleton fiber constituting the nonwoven fabric, ultrafine fibers with a fiber diameter of 3.0 μm were used, and as the functional fiber and adhesive fiber, the flat fiber (crystallinity: 36%, melting point: 254°C) and adhesive fiber used in Example 13 were used, and papermaking was carried out in a ratio of functional fiber / adhesive fiber / other fiber = 40 wt % / 30 wt % / 30 wt %. Except for this, the process was carried out in accordance with Example 10.
[0298] As a result, a nonwoven fabric having a structure in which flat fibers bridged between ultrafine fibers as skeleton fibers was obtained, and a complex void structure was formed between the fibers, resulting in a nonwoven fabric having excellent rigidity compared with Example 10. The results are shown in Table 5.
[0299] [Examples 19 and 20]
[0300] The component A is composed of polyethylene terephthalate (PET), and the component B is composed of polyethylene terephthalate copolymerized with 8.0 mol% of 5-sodium sulfonatoisophthalic acid and 9 wt% of polyethylene glycol (SSIA-PEG copolymerized PET). Figure 3The multilayer laminated fibers formed by alternately laminating the two polymers shown in the figure in one direction were cut to a fiber length of 1.0 mm (Example 19) and 5.0 mm (Example 20). The multilayer laminated fibers were respectively eluted with component B by the same method as in Example 10 to obtain a dispersion containing flat fibers (minor axis length: 500 nm) with a flatness of 40 and different fiber lengths. The dispersion was used to make paper with a unit area weight of 5.0 g / m 2 .
[0301] The obtained nonwoven fabric has a uniformly oriented flat fiber (crystallinity: 36%, melting point: 254°C) structure with a dense cross-sectional direction. Although the thickness is very thin, the rigidity of the sheet increases as the fiber length of the functional fiber increases, and the smoothness of the sheet surface also increases. The results are shown in Table 5.
[0302] Table 5
[0303]
[0304] Note 1) PET: Polyethylene terephthalate, Note 2) Fiber diameter: 3.0 μm
[0305] [Reference Example 1]
[0306] Melt spinning of polyethylene terephthalate (PET, melt viscosity: 120 Pa·s, melting point: 254°C, SP value: 21.4 MPa) at 290°C 1 / 2 ). The ejected polymer stream was cooled and solidified, and then an oil agent was applied, and the spinning speed was 1000 m / min to collect undrawn yarns of 200 dtex-72 filaments (total ejection amount 20 g / min). The wound undrawn fibers were stretched 3.6 times between rollers heated to 90°C and 130°C to obtain drawn fibers of 56 dtex-72 filaments. Then, the drawn fibers were cut with a cutter to obtain short fibers with an average fiber length of 5 mm.
[0307] [Reference Example 2]
[0308] Polyphenylene sulfide (PPS, melt viscosity: 130 Pa·s, melting point: 283°C, SP value: 25.8 MPa) consisting only of p-phenylene sulfide units 1 / 2) was melt-spun at 310°C. The ejected polymer stream was cooled and solidified, and then an oil agent was added. The unstretched yarn of 200 dtex-72 filaments (total ejection amount 20 g / min) was collected at a spinning speed of 1000 m / min. The wound unstretched fiber was stretched 3.6 times between rollers heated to 90°C and 200°C to obtain a stretched fiber of 56 dtex-72 filaments. Then, the stretched fiber was cut with a cutter to obtain a short fiber with an average fiber length of 5 mm.
[0309] [Example 21]
[0310] As component A, polyethylene terephthalate (PET, melt viscosity: 120 Pa·s, melting point: 254° C., SP value: 21.4 MPa) was prepared. 1 / 2 ), as component B, polyethylene terephthalate (SSIA-PEG copolymer PET, melt viscosity: 95 Pa·s, melting point: 233°C, SP value: 22.9 MPa) copolymerized with 8.0 mol% of 5-sodium sulfonate isophthalic acid and 9 wt% of polyethylene glycol was prepared. 1 / 2 ). In addition, the solubility parameter difference between these polymers is 1.5 MPa 1 / 2 .
[0311] After the components A and B were melted at 290°C, the composite ratio of the components A and B was 80 / 20, and poured into the assembled Figure 4 The spinning assembly of the composite die shown in the figure ejects the composite polymer flow from the ejection hole. In addition, a fine flow path G capable of alternately stacking 64 layers of two components is used on the composite plate, such as Figure 3 As shown, two polymers are ejected in a composite form in which multiple layers are alternately stacked in one direction. The ejected composite polymer stream is cooled and solidified, and then an oil agent is applied, and the spinning speed is 1000 m / min to collect undrawn yarns of 100 dtex-24 filaments (total ejection amount 10 g / min).
[0312] The obtained multilayer laminated fiber was cut into a fiber length of 5.0 mm, and the cut multilayer laminated fiber was immersed in a 1 wt % sodium hydroxide aqueous solution (bath ratio 1 / 100) heated to 70° C. for 30 minutes to dissolve and remove more than 99% of the easily soluble polymer SSIA-PEG copolymer PET, thereby obtaining Figure 1 The cross section shown is a short fiber (melting point: 254° C.) in a flat shape.
[0313] The specific surface area was measured based on the cross section of the obtained short fibers and was found to be 0.0041 nm. -1, which is very large. The cross-sectional morphology is a ribbon-shaped cross-section with significantly different lengths of the major axis and the minor axis, with a flatness of 40, a minor axis of 500nm, and a major axis of 20000nm. In addition, the variation of the length of the minor axis of the cross section is 32%, and the concavity is 21%. The length of the minor axis has a suitable variation, and the surface has moderate concavity. In addition, the crystallinity is 6%, which is amorphous, and the tanδ is 0.25, showing high fluidity.
[0314] The above short fibers as binder fibers were mixed at a ratio of 50% by mass and the short fibers obtained in Reference Example 1 as the bonded material in a ratio of 50% by mass in a papermaking dispersion to prepare a fiber concentration of 0.4% by mass. The papermaking liquid was supplied to a square sheet machine (250 mm square) manufactured by Kumagai Riki Industry Co., Ltd. to obtain a sheet with a unit area weight of 5 g / m 2 Furthermore, the sheets were heat-pressed at a pressure of 1.0 MPa for 1 minute using a flat plate heating press at 200°C to obtain a nonwoven fabric.
[0315] The obtained nonwoven fabric had no agglomerates such as fiber lumps and had a good texture. Although it was thin and had a low weight per unit area, it had a good strength of 2.40 N / 15 mm. The results are shown in Table 6.
[0316] [Examples 22 and 23]
[0317] In the method described in Example 21, all the steps were carried out in the same manner as in Example 21, except that the composite plate having the microchannels was changed to a composite plate having 32 layers (Example 22) and 16 layers (Example 23) of two components stacked. These multi-layered fibers were subjected to the same cutting and dissolving treatment as above to obtain Figure 1 The cross-sectional shape shown is a flat short fiber (melting point: 254°C). The evaluation results of these short fibers are shown in Table 6. Examples 22 and 23 have a large specific surface area. In addition, the cross-sectional shape is an extremely thin band with high flatness, and has an appropriate variation and unevenness of the short axis length. When evaluated as a sheet, compared with Example 21, as the flatness decreases and the average length of the short axis increases, the bonding rate decreases slightly, and the variation of the bonding rate increases slightly, but even with a thin texture and a low unit area weight, it can still exert excellent strength.
[0318] [Examples 24 and 25]
[0319] In the method described in Example 22, all the steps were carried out in the same manner as in Example 22, except that the temperature of the dissolution treatment when removing the easily soluble polymer was set to 75°C (Example 24) and 80°C (Example 25). The evaluation results are shown in Table 6. Compared with Example 22, the temperature of the dissolution treatment was increased, the crystallinity of the short fibers (melting point: 254°C) increased, and tanδ decreased. When the nonwoven fabric was made, the crystallinity increased and the fluidity decreased compared with Example 22, thereby decreasing the bonding rate and increasing the variability of the bonding rate, but the excellent strength was maintained.
[0320] [Examples 26 and 27]
[0321] In the method described in Example 22, all the steps were carried out in the same manner as in Example 22, except that a composite plate having a different flow path structure from that of the micro-flow path G was used. The results obtained are shown in Table 6. The composite plate has the same extremely thin cross-sectional shape with high flatness as in Example 22, but by changing the flow path structure of the composite plate, short fibers (Example 26) with a small cross-sectional variation in the length of the short axis and short fibers (Example 27) with a small cross-sectional unevenness were obtained. When the nonwoven fabric was made for evaluation, there were no fiber lumps in the nonwoven fabric and it was homogeneous, but the bonding rate was slightly reduced compared to Example 22, and the bonding rate variation increased, but the strength was excellent. In addition, the melting point of the short fibers of Examples 26 and 27 was 254°C.
[0322] [Comparative Example 7]
[0323] Except for using the undrawn yarn (melting point: 254°C) described in Reference Example 1 as the binder fiber, all the operations were carried out in the same manner as in Example 21. The evaluation results are as follows. The fiber cross section was circular, the specific surface area was small, and when it was made into a nonwoven fabric, it was uneven with damage or pinholes everywhere, the bonding rate was extremely variable, and the strength was significantly low. In addition, since it was an uneven nonwoven fabric, the average pore size and arithmetic mean roughness were not measured.
[0324] [Comparative Example 8]
[0325] In the method described in Example 22, all the steps were carried out in the same manner as in Example 22, except that the multi-layered laminated fibers were placed in a hot air dryer heated to 120°C for 30 minutes to be thermally crystallized in advance and then subjected to a dissolution treatment at 90°C for 30 minutes. The evaluation results are shown in Table 6. The obtained short fibers (melting point: 254°C) had a crystallinity as high as 36%. When the short fibers were made into nonwoven fabrics, they were uneven with damage or pinholes everywhere, the bonding rate had a large variation, and the strength was significantly low.
[0326]
[0327] [Examples 28 and 29]
[0328] In the methods described in Examples 22 and 23, component A is polyphenylene sulfide (PPS, melt viscosity: 130 Pa·s, melting point: 283° C., SP value: 25.8 MPa) consisting only of p-phenylene sulfide units. 1 / 2 ), component B is polyethylene terephthalate copolymerized with 5.0 mol% of 5-sodium sulfonate isophthalic acid (SSIA copolymer PET, melt viscosity: 130 Pa·s, melting point: 245°C), ejected at 310°C, and the ejected composite polymer flow is solidified, and then an oil agent is applied. The unstretched yarn of 100 dtex-24 filaments (total ejection amount 10 g / min) is collected by winding at a spinning speed of 1000 m / min.
[0329] The obtained undrawn yarn was immersed in a 3 wt% sodium hydroxide aqueous solution (bath ratio 1 / 100) heated to 60°C for 40 minutes for dissolution treatment, and more than 99% of the easily soluble polymer SSIA copolymer PET was dissolved and removed to obtain Figure 1 The short fibers shown have a flat cross section. In addition, 0.5 wt % of DY-1125K (quaternary ammonium salt type cationic surfactant) manufactured by Life Science Chemikals Co., Ltd. was added as a dissolution accelerator to the sodium hydroxide aqueous solution relative to the mass of the sodium hydroxide aqueous solution.
[0330] The above thermoplastic fiber as a binder fiber was mixed at a ratio of 50% by mass and the short fiber obtained in Reference Example 2 as an adhesive material was mixed at a ratio of 50% by mass in a papermaking dispersion to prepare a fiber concentration of 0.4% by mass. The papermaking liquid was supplied to a simple papermaking machine to obtain a paper having a unit weight of 5 g / m 2 Furthermore, the sheets were heat-pressed at 220°C and a pressing pressure of 1.0 MPa for 1 minute.
[0331] The evaluation results of the obtained short fibers (melting point: 283°C) are shown in Table 7. However, Examples 28 and 29 have a large specific surface area, and the cross-sectional shape is an extremely thin ribbon with high flatness, and has appropriate variation and unevenness of the minor axis length. When the nonwoven fabric was made and evaluated, there was no fiber block in the nonwoven fabric, and the nonwoven fabric was uniform, had a high bonding rate, a low degree of variation in bonding rate, and excellent strength.
[0332] [Example 30]
[0333] In the method described in Example 28, all the steps were carried out in the same manner as in Example 28, except that the temperature of the dissolution treatment when removing the easily soluble polymer was set to 90°C. The evaluation results are shown in Table 7. Compared with Example 28, the temperature of the dissolution treatment was increased, the crystallinity of the short fibers (melting point: 283°C) increased, and tanδ decreased. When the nonwoven fabric was made, the crystallinity increased compared with Example 28, thereby reducing the bonding rate and increasing the variability of the bonding rate, but maintaining excellent strength.
[0334] [Comparative Example 9]
[0335] The same procedures as in Example 28 were followed except that the undrawn yarn (melting point: 283° C.) described in Reference Example 2 was used as the binder fiber. The evaluation results are as follows: the fiber cross section was circular, the specific surface area was small, and when the fiber was made into a nonwoven fabric, it was uneven with damage or pinholes everywhere, the bonding rate varied greatly, and the strength was significantly low.
[0336] Table 7
[0337] Note 1) PPS: Polyethylene terephthalate, Note 2) Fiber diameter
[0338] Description of the accompanying drawings
[0339] A: Short fiber
[0340] B: A ingredients
[0341] C:B ingredients
[0342] D: Metering plate
[0343] E: Composite board
[0344] F: ejection plate
[0345] G: Micro flow path
[0346] Industrial Applicability
[0347] The fiber dispersion in which the short fibers of the present invention are uniformly dispersed in a medium can not only be directly utilized as a high-performance adsorbent material or reinforcing material, but also can be widely used as an industrial material as a high-performance filter material or separation membrane, sound-absorbing material, etc. when the medium is removed from the dispersion by a wet papermaking method or a spray method and the dispersion is made into sheets.
Claims
1. A short fiber having a flatness (a value obtained by dividing the length of the major axis of a fiber cross section by the length of the minor axis) of 5 or more, and an average value of the minor axis length of 2000 nm or less.
2. The short fiber as described in claim 1, wherein the CV value, which is the variation in the length of the minor axis of the fiber cross section, is greater than 10%.
3. The short fiber according to claim 1 or 2, wherein the roughness of the fiber cross section is 20% or more. The short fibers according to claim 1 , having a crystallinity of 20% or less.
5. The short fiber according to claim 4, having a melting point of 180°C or higher.
6. A fiber dispersion liquid, which is obtained by dispersing the short fibers according to claim 1 or 4 in an aqueous medium.
7. A nonwoven fabric comprising the short fibers according to claim 1 or 4 in at least a part thereof.
8. A nonwoven fabric having a density of 0.4 g / cm 3 The average pore size is 6 μm or less, and the maximum frequency of the pore size distribution is 30% or less. 9 . The nonwoven fabric according to claim 8 , wherein the arithmetic mean roughness Ra of the surface is 5.00 μm or less.
10. A fiber product comprising the nonwoven fabric according to claim 7 or 8 in at least a part thereof.
Citation Information
Patent Citations
Method for producing short-cut nanofiber and wet nonwoven fabric
JP2007107160A
Ultrafine flat short fiber and water dispersion comprising the same
JP2018084008A
Ultrafine fibers and liquid fiber dispersion
WO2020101002A1